Active energy ray-curable composition

JP2025039585A5Pending Publication Date: 2025-11-20KJ CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024226931
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-17
Filing Date
2024-12-24
Publication Date
2025-11-20

AI Technical Summary

Technical Problem

Existing active energy ray curable compositions struggle to achieve high transparency, high curability, and low curing shrinkage simultaneously, particularly when used in optical materials where transparency and durability are critical.

Method used

The use of a (meth)acrylate (A) with an amide group and a cyclic substituent, combined with a polymerizable compound (B) that includes a chain substituent or a cyclic substituent, to create an active energy ray curable composition that balances amphiphilicity and curability, thereby enhancing transparency and reducing curing shrinkage.

Benefits of technology

The proposed composition achieves high transparency, excellent heat resistance, durability, and impact resistance in the cured product, while maintaining high curability and low curing shrinkage, making it suitable for a wide range of applications including optical materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an active energy ray-curable composition having various characteristics required for an active energy ray-curable composition and capable of achieving high transparency, high curability to LED light beam and hardening shrinkage resistance, which were difficult to achieve together, and a cured product capable of achieving together transparency, heat resistance, impact resistance, wear resistance, resistance to heat and humidity yellowing, water resistance and endurance, which were difficult to achieve together.SOLUTION: An active energy ray-curable composition containing (A) a (meth)acrylate with an amide group and a cyclic substituent in the molecule, and (B) a polymerizable compound containing one or more ethylenically unsaturated groups in the molecule (excluding A), and at least a polymerizable compound (b1) with a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) with a cyclic substituent having 3 to 20 carbon atoms.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable composition, a curable ink composition, a pressure-sensitive adhesive composition, an adhesive composition, a sealant composition, a paint composition, a nail cosmetic, a decorative coating agent, a dental material, and a cured product obtained by curing them, each of which contains the active energy ray-curable composition. [Background technology]

[0002] An active energy ray-curable composition generally comprises a plurality of polymerizable components and a photopolymerization initiator, and is solidified (cured) from a liquid state at room temperature in a short time by irradiation with active energy rays such as ultraviolet rays (UV) or electron beams (EB), and is used in a wide range of fields such as coating agents, paints, pressure sensitive adhesives, adhesives, elastomer materials, materials for flexible displays, inkjet inks, sealing materials and sealants, dental hygiene materials, optical materials, etc. In particular, because it can be cured at any location or shape, it is being widely used as nail cosmetics such as gel nails and as materials for two-dimensional or three-dimensional photolithography.

[0003] Active energy ray curable compositions are required to have various performances depending on the field and environment in which they are used, and in order to meet these requirements, it is necessary to combine a wide variety of polymerizable components. In general, polymerizable oligomers (prepolymers) such as urethane acrylate and epoxy acrylate, polyfunctional monomers, monofunctional monomers, and photopolymerization initiators are blended as main components, and additives such as fillers, pigments and dyes, leveling agents, viscosity modifiers, and polymerization inhibitors can be added depending on the application. For example, Patent Document 1 describes an active energy ray curable composition containing (meth)acrylates having an alicyclic skeleton as monofunctional monomers, N-substituted (meth)acrylamides, (meth)acrylates having linear or branched alkyl groups with 8 to 18 carbon atoms, (meth)acrylates having a urethane group as polymerizable oligomers, and a photopolymerization initiator. It has been proposed to provide a cured product that can achieve both high elongation and high elastic modulus at a high level by blending these components in a specific ratio. The patent document discloses that monofunctional (meth)acrylates having an alicyclic skeleton and monofunctional (meth)acrylates having a linear or branched alkyl group with 8 to 18 carbon atoms are preferred from the viewpoint of elongation and elastic modulus of the cured product, N-substituted (meth)acrylamides having an extremely short alkyl group such as dimethyl or diethyl are preferred from the viewpoint of curability, and urethane (meth)acrylates having 1 to 2 (meth)acryl groups are preferred from the viewpoint of elongation of the cured product. However, there is no mention of the transparency of the curable composition and the transparency, heat resistance, impact resistance, durability, water resistance, etc. of the obtained cured product. Both (meth)acrylates having an alicyclic skeleton and (meth)acrylates having a linear or branched alkyl group with 8 to 18 carbon atoms are highly hydrophobic and have high steric hindrance, and therefore have low curability, while N-substituted (meth)acrylamides having a short alkyl group are known to have high hydrophilicity and curability. With such a combination of components, it is not expected that the curable composition and its cured product will show good transparency, and there is a problem that they are difficult to use in the optical field such as optical members.Furthermore, due to differences in curing properties, the molecular level structure of the obtained cured product becomes non-uniform, shrinkage during curing becomes large, and internal stress and distortion are easily generated in the obtained cured product, which causes a problem that sufficient durability, impact resistance and heat resistance cannot be provided for use as a paint, pressure sensitive adhesive, adhesive, electronic material, dental material, three-dimensional modeled object, etc.

[0004] Patent Document 2 describes an active energy ray-curable resin composition containing a polycyclic carboxamide having a (meth)acryloyl group. The curable resin composition described in the patent document has good UV curability, and the obtained cured film has good surface hardness as a hard coat. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-123720 [Patent Document 2] JP 2018-95626 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a novel active energy ray-curable composition that has a wide variety of properties required of an active energy ray-curable composition, and in particular is capable of simultaneously achieving high transparency, high curability against LED light rays, and cure shrinkage resistance, which have been difficult to achieve simultaneously in the past.

[0007] Another object of the present invention is to provide a cured product of an active energy ray-curable composition that has a wide variety of properties required for the cured product, and in particular, that can simultaneously achieve transparency, heat resistance, impact resistance, water resistance, durability and impact resistance, which have been difficult to achieve simultaneously in the past. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by an active energy ray-curable composition comprising a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule, and a polymerizable compound (B) (excluding A) having one or more ethylenically unsaturated groups in the molecule, and containing, as the polymerizable compound (B), a polymerizable compound (b1) having a chain substituent having at least 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms, and have completed the present invention.

[0009] That is, the present invention is based on the following configuration. (1) a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule; An active energy ray-curable composition containing a polymerizable compound (B) (excluding A) having one or more ethylenically unsaturated groups in the molecule, The polymerizable compound (B) is an active energy ray-curable composition containing a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms. (2) The active energy ray-curable composition according to (1) above, wherein the (meth)acrylate (A) has, as a cyclic substituent, one or more substituents selected from a saturated or unsaturated polycyclic aliphatic ring, a monocyclic or polycyclic aromatic ring, a saturated or unsaturated aliphatic heterocycle, and an aromatic heterocycle. (3) The active energy ray-curable composition according to (1) or (2), wherein the (meth)acrylate (A) has an amide group between the (meth)acrylate group and the cyclic substituent. (4) The active energy ray-curable composition according to any one of (1) to (3), wherein the polymerizable compound (B) has, as the ethylenically unsaturated group, one or more groups selected from a (meth)acrylamide group, a (meth)acrylate group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group and a maleimide group. (5) The active energy ray-curable composition according to any one of (1) to (4), wherein the content of the (meth)acrylate (A) is 0.1 to 99.5 mass%, the content of the polymerizable compound (b1) is 0.3 to 80 mass%, and the content of the polymerizable compound (b2) is 0.2 to 70 mass%, based on the entire active energy ray-curable composition. (6) The active energy ray-curable composition according to any one of (1) to (5), which has a cure shrinkage rate of 5% or less. (7) The active energy ray-curable composition according to any one of (1) to (6), wherein a cured product of the active energy ray-curable composition has a saturated water absorption of 10% or less. (8) An ink composition comprising the active energy ray-curable composition according to any one of (1) to (7) above. (9) An ink composition for two-dimensional or three-dimensional modeling, comprising the active energy ray-curable composition according to any one of (1) to (7) above. (10) A pressure-sensitive adhesive composition comprising the active energy ray-curable composition according to any one of (1) to (7). (11) An adhesive composition comprising the active energy ray-curable composition according to any one of (1) to (7) above. (12) A coating composition comprising the active energy ray-curable composition according to any one of (1) to (7). (13) A sealant composition comprising the active energy ray-curable composition according to any one of (1) to (7). (14) A nail cosmetic comprising the active energy ray-curable composition according to any one of (1) to (7) above. (15) A decorative coating agent comprising the active energy ray-curable composition according to any one of (1) to (7) above. (16) A dental material comprising the active energy ray-curable composition according to any one of (1) to (7). Effect of the Invention

[0010] According to the present invention, an active energy ray curable composition containing a (meth)acrylate (A) having a specific structure and a polymerizable compound (B) excluding A exhibits good compatibility with various Bs ranging from hydrophobic to hydrophilic and from monofunctional to polyfunctional due to the well-balanced amphiphilicity and high curability of A, and has high transparency and curability. In addition, by containing a polymerizable compound (b1) having a cyclic substituent in the molecule of the (meth)acrylate (A) and having a chain-like substituent with 1 to 36 carbon atoms as the polymerizable compound (B), it becomes easy to fill or arrange the chain-like substituent derived from b1 between or around the cyclic substituent derived from A, and the volumetric shrinkage during the curing process of the active energy ray curable composition can be suppressed to a low level. When the active energy ray curable composition contains a polymerizable compound (b2) having a cyclic substituent with 3 to 20 carbon atoms as the polymerizable compound (B), both the (meth)acrylate (A) and b2 have bulky cyclic substituents, so that the volumetric shrinkage during the curing process is low, and the transparency and heat resistance of the obtained cured product are excellent. Furthermore, by simultaneously containing the polymerizable compound (b1) and the polymerizable compound (b2), the steric hindrance of the cyclic substituent of the (meth)acrylate (A) and b2 is eliminated by the chain substituent of b1, and the active energy ray-curable composition containing A, b1, and b2 has high curability, low cure shrinkage, and is easily able to maintain a good compatibility state, and the obtained cured product has good transparency, heat resistance, and durability.

[0011] The (meth)acrylate (A) has a cyclic substituent in the molecule and has a high refractive index. Due to the interaction between the cyclic substituent and the amide group in the molecule, the homopolymer of the (meth)acrylate (A) has a higher glass transition temperature (Tg) than that of a normal cyclic polymer. In the cured product obtained from the active energy ray curable composition containing the (meth)acrylate (A) of such a specific structure and the polymerizable compound (B), high transparency, heat resistance, durability and impact resistance were realized. In addition, as a heterogeneous effect of the interaction between the amide group of the (meth)acrylate (A) and the cyclic substituent, the cured product obtained from the active energy ray curable composition of the present invention had high yellowing resistance and water resistance, despite having an amide group that is usually recognized as being easily colored and having low water resistance. When the (meth)acrylate (A) has an unsaturated polycyclic aliphatic ring and / or an unsaturated aliphatic heterocycle, the unsaturated bonds in the ring undergo partial polymerization upon exposure to active energy rays, and A becomes a special monomer between monofunctional and polyfunctional, and the resulting cured product has excellent impact resistance.

[0012] The active energy ray curable composition of the present invention has high curability against the light (wavelength range 250 to 450 nm) of a general-purpose UV ink curing metal halide lamp and against the light (wavelength 365 nm, 385 nm, 395 nm, 405 nm) of a highly safe LED, and the liquid viscosity of the curable composition can be adjusted almost without limit from low viscosity to high viscosity depending on the application, and can be provided as a curable ink composition for printing such as inkjet printing, screen printing, offset printing, flexographic printing, etc., and a curable ink composition for two-dimensional or three-dimensional modeling. In addition, the active energy ray curable composition of the present invention has high wettability and adhesion to various substrates from low-polarity plastics to high-polarity glass and metals, and can be provided as a curable adhesive composition, adhesive composition, paint composition, sealant composition, nail cosmetic, decorative coating agent used in decorative films and decorative sheets, dental materials, etc. Furthermore, when the (meth)acrylate (A) has an unsaturated polycyclic aliphatic ring and / or an unsaturated aliphatic heterocycle, the (meth)acrylate group can be polymerized by photopolymerization, and then these unsaturated groups can be polymerized by thermal polymerization. Thus, the active energy ray-curable composition of the present invention is suitably used for bonding opaque materials such as metals, bonding different materials, and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail. The first to fifth embodiments of the present invention (hereinafter collectively referred to as the present embodiments) are active energy ray-curable compositions (E). The active energy ray-curable compositions (E) according to the present embodiments (hereinafter also simply referred to as "curable compositions (E)") contain a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule, and a polymerizable compound (B) (excluding A) having one or more ethylenically unsaturated groups in the molecule, and contain a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms as B and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms as B.

[0014] By containing the (meth)acrylate (A), the active energy ray curable composition (E) has high curability while suppressing the cure shrinkage when curing E. The interaction between A and B improves the transparency of E, further reduces the cure shrinkage of E, and the cured product of E has high yellowing resistance and water resistance. Furthermore, by containing A and the b2, the cured product of E has high heat resistance and durability.

[0015] With respect to the total mass of the active energy ray curable composition (E), the content of (meth)acrylate (A) is preferably 0.1 to 99.5 mass%, the content of polymerizable compound (b1) is preferably 0.3 to 80 mass%, and the content of polymerizable compound (b2) is preferably 0.2 to 70 mass%, and the sum of the contents of b1 and b2 is more preferably 0.5 mass% or more. If the contents of A, b1, and b2 are within these ranges, the transparency, curability, and cure shrinkage resistance of E can be simultaneously achieved, and the transparency, heat resistance, yellowing resistance, durability, and water resistance of the obtained cured product can be simultaneously achieved. In addition, from the viewpoint of simultaneously achieving the above-mentioned various properties and high performance in E and its cured product, the content of A is more preferably 1 to 95 mass%, the content of b1 is 5 to 70 mass%, and the content of b2 is 2 to 60 mass%, and it is particularly preferable that the content of A is 5 to 90 mass%, the content of b1 is 10 to 60 mass%, and the content of b2 is 5 to 50 mass%.

[0016] The (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule is not particularly limited as long as it is a compound having one or more amide groups and one or more cyclic substituents in the molecule, and one or more methacrylate groups and / or acrylate groups. The cyclic substituent is one or more substituents selected from monocyclic or polycyclic aliphatic rings, monocyclic or polycyclic aromatic rings, aliphatic heterocycles, and aromatic heterocycles, and these substituents may be saturated or unsaturated rings, such as cyclohexyl group, dicyclopentanyl group, dicyclopentenyl group, bornyl group, isobornyl group, adamantyl group, norbornane group, norbornene group, oxanorbornane group, oxanorbornene group, azanorbornane group, azanorbornene group, tricyclodecane group, phenyl group, naphthalene group, triphenylene group, pyrene group, perylene group, indacene group, biphenylene group, acenaphthylene group, phenalene group, anthracene group, cyclohexylphenyl group, 4-morpholinophenyl group, various bisphenol groups, bisoxazoline group, etc. These cyclic substituents may be one type only, or two or more types may be included.

[0017] The (meth)acrylate (A) may further have a substituent (R) on the cyclic substituent. The substituent R is a linear alkyl group or hydroxyalkylene group having 1 to 6 carbon atoms, an alkenyl group or alkyleneoxyalkyl group having 2 to 6 carbon atoms, or a branched alkyl group having 3 to 6 carbon atoms, which may be substituted with an ethylenically unsaturated bond, and the ethylenically unsaturated group in R is one or more groups selected from the group consisting of a (meth)acrylate group, a (meth)acrylamide group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group, and a maleimide group. The cyclic substituent of A may be a saturated ring or an unsaturated ring. It is preferable that the cyclic substituent of A is an unsaturated ring and / or the substituent R has an ethylenically unsaturated group. In this preferable case, A has two or more unsaturated groups in the molecule, which enhances the curability of the active energy ray curable composition (E), and further improves the heat resistance, durability, water resistance, etc. of the obtained cured product. Moreover, it is more preferable that the unsaturated group of the unsaturated ring of A and / or the ethylenically unsaturated group of the substituent R are groups other than (meth)methacrylate groups. In this more preferable case, A has two or more unsaturated groups with different structures in the molecule, and by adjusting the type and intensity of the active energy ray, the two or more different unsaturated groups can be cured in sequence, and it is possible to gradually increase the crosslinking rate of the cured product while suppressing the cure shrinkage rate, and a cured product having excellent impact resistance can be obtained.

[0018] The amide group of the (meth)acrylate (A) may be a secondary amide group (N-substituted amide), a tertiary amide group (N,N-disubstituted amide), a diacetamide group, an N-substituted diacetamide group, or the like. It is preferable that A has an amide group between the (meth)acrylate group and the cyclic substituent. In this case, the effect of the interaction between the amide group and the (meth)acrylate group and / or the interaction between the amide group and the cyclic substituent can be more efficiently expressed than when each of these groups acts alone. It is preferable that A has a (meth)acrylate group and an amide group linked by a linear or branched alkylene group (first linking group) having 1 to 6 carbon atoms, and the amide group and the cyclic substituent are directly linked or linked by a linear or branched alkylene group (second linking group) having 1 to 6 carbon atoms. In addition, when the (meth)acrylate group and the amide group are linked by a linear alkylene group having 2 to 4 carbon atoms and the amide group and the cyclic substituent are directly linked, the curability of the (meth)acrylate group against active energy rays is improved, and yellowing of the cured product over time caused by the amide group is reduced, which is more preferable. Furthermore, when the cyclic substituent is an unsaturated ring, the curability against active energy rays is further improved, which is particularly preferable.

[0019] The (meth)acrylate (A) can be synthesized by a known method. In general, examples of the method include a method in which a carboxylic acid, carboxylic acid ester, carboxylic acid chloride, or carboxylic acid anhydride having a cyclic substituent is subjected to an amidation reaction with a compound having a hydroxy group and an amino group, such as an alkanolamine, to obtain a carboxamide compound having a hydroxy group and a cyclic substituent, and then the carboxamide compound is subjected to an esterification reaction with (meth)acrylic anhydride or (meth)acrylic acid or an ester exchange reaction with a lower alkyl (meth)acrylic ester; and a method in which an N-substituted amide or N,N-disubstituted amide substituted with a cyclic substituent having a hydroxy group is subjected to an esterification reaction with (meth)acrylic anhydride or (meth)acrylic acid, or an ester exchange reaction with a lower alkyl (meth)acrylic ester.

[0020] The (meth)acrylate (A) is, for example, a (meth)acryloyloxyalkylenenorbornanecarboxamide such as (meth)acryloyloxymethylenenorbornanecarboxamide, (meth)acryloyloxyethylenenorbornanecarboxamide, (meth)acryloyloxy(iso)propylenenorbornanecarboxamide, (meth)acryloyloxy(iso)butylenenorbornanecarboxamide, (meth)acryloyloxy(iso)amylenenorbornanecarboxamide, or (meth)acryloyloxy(iso)hexylenenorbornanecarboxamide, (meth)acryloyloxymethylenebornanecarboxamide, (meth)acryloyloxyethylenenorbornanecarboxamide, (meth)acryloyloxy(iso)propylenenorbornanecarboxamide, (meth)acryloyloxy(iso)butylenenorbornanecarboxamide, (meth)acryloyloxy(iso)amylenenorbornanecarboxamide, or (meth)acryloyloxy(iso)hexylenenorbornanecarboxamide. (meth)acryloyloxyalkylenenorbornenecarboxamides such as (meth)acryloyloxy(iso)butylenenorbornenecarboxamide, (meth)acryloyloxy(iso)amylenenorbornenecarboxamide, and (meth)acryloyloxy(iso)hexylenenorbornenecarboxamide; (meth)acryloyloxymethyleneoxanorbornanecarboxamide; (meth)acryloyloxyethyleneoxanorbornanecarboxamide; and (meth)acryloyloxy(iso)propyleneoxanorbornanecarboxamide. (meth)acryloyloxyalkylene oxanorbornane carboxamides such as (meth)acryloyloxy(iso)butylene oxanorbornane carboxamide, (meth)acryloyloxy(iso)amylene oxanorbornane carboxamide, and (meth)acryloyloxy(iso)hexylene oxanorbornane carboxamide; (meth)acryloyloxymethylene oxanorbornene carboxamide; (meth)acryloyloxyethylene oxanorbornene carboxamide; and (meth)acryloyloxy(iso)propylene oxanorbornene carboxamide.(meth)acryloyloxyalkylene oxanorbornene carboxamides such as (meth)acryloyloxy(iso)butylene oxanorbornene carboxamide, (meth)acryloyloxy(iso)amylene oxanorbornene carboxamide, and (meth)acryloyloxy(iso)hexylene oxanorbornene carboxamide; (meth)acryloyloxyalkylene (carbon number 1-6) norbornene-2-alkyl (carbon number 1-6)-2-carboxamides; (meth)acryloyloxyalkylene (carbon number 1-6) dicyclopentenyl carboxamide; (meth)acryloyloxyalkylene (carbon number 1-6) dicyclopentanyl carboxamide; (meth)acryloyloxyalkylene (carbon number 1-6), alkyl (carbon number 1-6); Examples of the acryloyloxyalkylene dicarboxyamide include dicyclopentanyl dicarboxyamide, bis(meth)acryloyloxyalkylene (carbon number: 1 to 6) dicyclopentanyl dicarboxyamide, (meth)acryloyloxyalkylene (carbon number: 1 to 6) isobornane carboxamide, and bis(meth)acryloyloxyalkylene (carbon number: 1 to 6) cyclohexane dicarboxyamide.

[0021] The polymerizable compound (B), other than the (meth)acrylate (A), is a compound having one or more ethylenically unsaturated groups in the molecule. The ethylenically unsaturated groups of B are one or more groups selected from the group consisting of (meth)acrylate groups, (meth)acrylamide groups, vinyl groups, vinyl ether groups, alkyl vinyl ether groups, allyl groups, (meth)allyl ether groups and maleimide groups, and from the viewpoint of high curability against active energy rays, are preferably acrylamide groups and acrylate groups. B contains a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms (excluding A and b1), and both b1 and b2 contain a monofunctional polymerizable compound (hereinafter also referred to as a monofunctional monomer) having one ethylenically unsaturated group in the molecule and a polyfunctional polymerizable compound (hereinafter also referred to as a polyfunctional monomer) having two or more ethylenically unsaturated groups in the molecule, and may also contain a polymerizable compound (b3) having one or more ethylenically unsaturated groups in the molecule, except for b1 and b2.

[0022] The active energy ray curable composition (E) according to this embodiment contains a polymerizable compound (b1) or a polymerizable compound (b2), and preferably contains both b1 and b2 from the viewpoint of further improving various physical properties. By containing b1 and b2, E can be optimized according to various applications, such as viscosity, pigment dispersibility, printability, etc. in an inkjet ink composition, modeling accuracy, modeling strength, etc. in a three-dimensional stereolithography curable composition, adhesion, reworkability, yellowing resistance, etc. in a pressure-sensitive adhesive composition, adhesion, impact resistance, etc. in an adhesive composition, wettability to a substrate in a coating composition, surface hardness of the resulting coating film, etc. From this viewpoint, the mass ratio of the contents of b1 and b2 is more preferably 30 / 1 to 1 / 10, and particularly preferably 10 / 1 to 1 / 5.

[0023] The polymerizable compound (b1) has one or more ethylenically unsaturated groups and a chain-like substituent having 1 to 36 carbon atoms in the molecule, and the chain-like substituent may be linear or branched, may be a saturated alkyl group or an unsaturated alkenyl group, and may have or be substituted with a hydroxyl group, a primary amino group, a secondary amino group, a tertiary amino group, a thiol group, an ether group, an ester group, a ketone group, a carboxylic acid group, an amide group, a sulfonic acid group, etc. The ethylenically unsaturated group of b1 is one or more ethylenically unsaturated groups selected from the group consisting of a (meth)acrylate group, a (meth)acrylamide group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group, and a maleimide group, and is preferably an acrylamide group and an acrylate group from the viewpoint of having high curability against active energy rays.

[0024] In the above b1, examples of the monofunctional polymerizable compound having an acrylamide group include linear or branched N-substituted alkylacrylamides having 1 to 36 carbon atoms, N,N-disubstituted dialkylacrylamides, linear or branched N-substituted alkenyl acrylamides having 1 to 36 carbon atoms, linear or branched N,N-disubstituted dialkenyl acrylamides having 1 to 36 carbon atoms, linear or branched N,N-disubstituted alkylalkenyl acrylamides having 1 to 36 carbon atoms; Examples of such an acrylamide include linear or branched N-substituted alkylacrylamides having 1 to 36 carbon atoms, N,N-disubstituted dialkylacrylamides, linear or branched N-substituted alkenyl acrylamides having 1 to 36 carbon atoms, linear or branched N,N-disubstituted dialkenyl acrylamides having 1 to 36 carbon atoms, and linear or branched N,N-disubstituted alkyl alkenyl acrylamides having 1 to 36 carbon atoms, which have or are substituted with an alkyl group, an ether group, an ester group, a ketone group, a carboxylic acid group, an amide group, a sulfonic acid group, or the like. Among these, from the viewpoint of easy availability of industrial products, etc., dimethylacrylamide, diethylacrylamide, isopropylacrylamide, t-butylacrylamide, ethylhexylacrylamide, n-octylacrylamide, t-octylacrylamide, oleylacrylamide, methoxybutylacrylamide, butoxymethylacrylamide, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-[3-(dimethylamino)]propylacrylamide, and diacetoneacrylamide are preferred. These monofunctional polymerizable compounds having an acrylamide group may be used alone or in combination of two or more.

[0025] In the above b1, examples of the polyfunctional polymerizable compound having an acrylamide group include methylene bis(meth)acrylamide, ethylene bis(meth)acrylamide, diallyl (meth)acrylamide, N-[tris(3-(meth)acrylamide propoxymethyl)methyl](meth)acrylamide, N,N-bis(2-(meth)acrylamide ethyl)(meth)acrylamide, 4,7,10-trioxa-1,13-tridecane bis(meth)acrylamide, N,N'-1,2-ethane dibis[N-(2-(meth)acrylamide ethyl)](meth)acrylamide, and other monomer-type polyfunctional polymerizable compounds having an acrylamide group, and oligomer-type polyfunctional polymerizable compounds having an acrylamide group, such as polyurethane diacrylamide having no cyclic substituent. These polyfunctional polymerizable compounds having an acrylamide group may be used alone or in combination of two or more.

[0026] In the above b1, examples of the monofunctional polymerizable compound having an acrylate group include linear or branched alkyl acrylates having 1 to 36 carbon atoms, linear or branched alkenyl acrylates having 1 to 36 carbon atoms, linear or branched alkyl acrylates having 1 to 36 carbon atoms, linear or branched alkenyl acrylates having 1 to 36 carbon atoms, each of which has or is substituted with one or more hydroxyl groups, primary to tertiary amino groups, thiol groups, ether groups, ester groups, ketone groups, carboxylic acid groups, amide groups, sulfonic acid groups, etc. Among these, from the viewpoint of easy availability of industrial products, examples thereof include butyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, hydroxyethyl acrylate, 4-hydroxybutyl acrylate, etc.

[0027] In the above b1, examples of the polyfunctional polymerizable compound having an acrylate group include ethylene glycol diacrylate, diethylene glycol diacrylate, methoxydipropylene glycol acrylate, methoxytripropylene glycol acrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol ethylene oxide modified diacrylate, hydroxypivalic acid neopentyl glycol diacrylate, glycerin diacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, pentaerythritol diacrylate, dipentaerythritol triacrylate, dipentaerythritol hematemyl acrylate, and the like. Examples of the polyfunctional polymerizable compound having an acrylate group of a monomer type, such as dipentaerythritol pentaacrylate, dipentaerythritol tetraacrylate, ethylene glycol diglycidyl ether diacrylate, diethylene glycol diglycidyl ether diacrylate, trimethylolethane triacrylate, trimethylolpropane triacrylate, etc., and a polyfunctional polymerizable compound having an acrylate group of an oligomer type, such as polyether diacrylates, such as polyethylene glycol diacrylate, polypropylene glycol diacrylate, polytetramethylene glycol diacrylate, etc., polyurethane diacrylate, polyester diacrylate, etc. These polyfunctional polymerizable compounds having an acrylate group may be used alone or in combination of two or more.

[0028] The polymerizable compound (b2) has one or more ethylenically unsaturated groups and a cyclic substituent having 3 to 20 carbon atoms in the molecule, and the cyclic substituent is one or more substituents selected from a monocyclic or polycyclic aliphatic ring, an aromatic ring, an aliphatic heterocycle, and a monocyclic or polycyclic aromatic heterocycle, and the aliphatic ring and the aliphatic heterocycle may be saturated or unsaturated rings. The ethylenically unsaturated group of b2 is one or more ethylenically unsaturated groups selected from the group consisting of a (meth)acrylate group, a (meth)acrylamide group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group, and a maleimide group, and is preferably an acrylamide group and an acrylate group from the viewpoint of having high curability against active energy rays. When the ethylenically unsaturated group of b2 is a (meth)acrylate group, it does not have an amide group in the molecule. When the ethylenically unsaturated group that b2 has is a (meth)acrylamide group, the molecule does not have a (meth)acrylate group.

[0029] In the above b2, examples of the monofunctional polymerizable compound having an acrylamide group include N-cyclohexyl acrylamide, N,N-dicyclohexyl acrylamide, N-cyclohexyl-N-methyl acrylamide, N-cyclohexyl-N-ethyl acrylamide, N-cyclohexyl-N-propyl acrylamide, N-cyclohexyl-N-butyl acrylamide, N-phenyl acrylamide, N-acryloyl morpholine, N-acryloyl piperidine, N-acryloyl-2-methyl piperidine, N-acryloyl morpholine ... N-acryloyl-3-methylpiperidine, N-acryloyl-4-methylpiperidine, N-acryloyl-2,6-dimethylpiperidine, N-acryloyl-3,5-dimethylpiperidine, N-acryloyl-3,3-dimethylpiperidine, N-acryloyl-4,4-dimethylpiperidine, N-acryloyl-2,2,6,6-tetramethylpiperidine, N-acryloyl-2-methyl-5-ethylpiperidine, N-acryloyl-4-methyl-4-ethylpiperidine, N-acryloyl-2-ethylpiperidine, N-acryloyl Acryloyl-3-ethylpiperidine, N-acryloyl-4-ethylpiperidine, N-acryloyl-2-propylpiperidine, N-acryloyl-3-propylpiperidine, N-acryloyl-4-propylpiperidine, N-acryloyl-3-isopropylpiperidine, N-acryloyl-4-isopropylpiperidine, N-acryloylhexamethyleneimine, N-acryloyl-2-methylhexamethyleneimine, N-acryloyl-3-methylhexamethyleneimine, N-acryloyl-4-methylhexamethyleneimine hexamethyleneimine, N-acryloyl-2-ethylhexamethyleneimine, N-acryloyl-3-ethylhexamethyleneimine, N-acryloyl-4-ethylhexamethyleneimine, N-acryloyl-3-propylhexamethyleneimine, N-acryloyl-4-propylhexamethyleneimine, N-acryloyl-3-isopropylhexamethyleneimine, N-acryloyl-4-isopropylhexamethyleneimine, N-acryloyl-3,5-dimethylhexamethyleneimine, N-acryloyl-4,Examples of the acryloyl hexamethyleneimine include 4-dimethylhexamethyleneimine, N-acryloylheptamethyleneimine, N-acryloyloctamethyleneimine, N-acryloyldecamethyleneimine, dopamine acrylamide, and 3-acrylamidophenylboronic acid. Among these, N-cyclohexyl acrylamide, N,N-dicyclohexyl acrylamide, N-cyclohexyl-N-methyl acrylamide, N-acryloyl morpholine, N-acryloyl piperidine, N-acryloyl-2-methyl piperidine, N-acryloyl-4-methyl piperidine, N-acryloyl-2,6-dimethyl piperidine, N-acryloyl-3,5-dimethyl piperidine, N-phenyl acrylamide, dopamine acrylamide, and 3-acrylamidophenylboronic acid are preferred from the viewpoint of easy availability of industrial products.

[0030] In the above b2, examples of the polyfunctional polymerizable compound having an acrylamide group include polyfunctional polymerizable compounds having an acrylamide group such as oligomer type polyurethane diacrylamide having a cyclic substituent. These polyfunctional polymerizable compounds having an acrylamide group may be used alone or in combination of two or more kinds.

[0031] In the b2, examples of the monofunctional polymerizable compound having an acrylate group include phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxytetraethylene glycol acrylate, phenoxyhexaethylene glycol acrylate, cyclohexyl acrylate, tert-butylcyclohexyl acrylate, benzyl acrylate, dicyclopentanyl acrylate, dicyclopentenyl acrylate, bornyl acrylate, isobornyl acrylate, tetrahydrofurfuryl acrylate, 2-methyl-2-adamantyl (meth)acrylate, etc. Among these, from the viewpoint of easy availability of industrial products, etc., phenoxyethyl acrylate, cyclohexyl acrylate, tert-butylcyclohexyl acrylate, dicyclopentanyl acrylate, dicyclopentenyl acrylate, isobornyl acrylate, and tetrahydrofurfuryl acrylate are preferred.

[0032] In the b2, examples of the polyfunctional polymerizable compound having an acrylate group include polyfunctional polymerizable compounds having monomer-type acrylate groups such as dicyclopentanyl diacrylate, caprolactone-modified dicyclopentenyl diacrylate, tricyclodecane dimethanol diacrylate, ethylene oxide-modified bisphenol A-type diacrylate, propylene oxide-modified bisphenol A-type diacrylate, and cyclohexane dimethanol diacrylate, and polyfunctional polymerizable compounds having oligomer-type acrylate groups such as polyurethane diacrylate having a cyclic substituent, polyester diacrylate having a cyclic substituent, and polyether diacrylate having a cyclic substituent. These polyfunctional polymerizable compounds having an acrylate group may be used alone or in combination of two or more.

[0033] The monofunctional polymerizable compound in the active energy ray curable composition (E), including the (meth)acrylate (A) and the polymerizable compound (B), is preferably 5 to 99% by mass based on the entire E. The polyfunctional polymerizable compound in E, including A and B, is preferably 1 to 95% by mass based on the entire E. If the monofunctional polymerizable compound and the polyfunctional polymerizable compound in E are within these ranges, it becomes possible to easily combine each compound having a different structure according to the purpose, and E can be suitably used for various applications. From this viewpoint, the total of the monofunctional polymerizable compound in E is more preferably 10 to 90% by mass, and particularly preferably 20 to 80% by mass. The total of the polyfunctional polymerizable compound in E is more preferably 5 to 90% by mass, and particularly preferably 10 to 80% by mass.

[0034] The sixth embodiment of the present invention is an active energy ray curable composition (E) having a volumetric shrinkage rate (curing shrinkage rate) occurring during the curing process in the active energy ray irradiation of 5% or less. Such E preferably contains 5% by mass or more of (meth)acrylate (A) and 60% by mass or less of a multifunctional polymerizable compound as a polymerizable compound (B) relative to the entire E, and more preferably contains 8% or more of A and 50% by mass or less of a multifunctional polymerizable compound as B. Furthermore, it is particularly preferable to contain 5% by mass or more of an oligomer type multifunctional polymerizable compound and / or 2% by mass or more of a polymer type multifunctional polymerizable compound as B relative to the entire E, since this can impart impact resistance to the obtained cured product while maintaining a low curing shrinkage rate.

[0035] The seventh embodiment of the present invention is an active energy ray curable composition (E) having a saturated water absorption rate of 10% or less in a cured product of the active energy curable composition. Such E preferably contains 5% by mass or more of (meth)acrylate (A) and 20% by mass or more of a compound having a chain or cyclic substituent having 6 or more carbon atoms as a polymerizable compound (B) relative to the whole of E, and more preferably contains 10% or more of A and 25% by mass or more of the b1 or b2 having a chain substituent having 6 or more carbon atoms as B. Furthermore, it has been confirmed that the water absorption rate of the obtained cured product is low and the durability of the cured product is improved at the same time, and it is particularly preferable that E contains 8% by mass or more of a compound having a chain or cyclic substituent having 6 or more carbon atoms as B and / or 3% by mass or more of the b1 or b2 having a chain substituent having 6 or more carbon atoms relative to the whole of E.

[0036] The eighth embodiment of the present invention is an ink composition (hereinafter, also referred to as ink). The ink composition contains the active energy ray curable composition (E) according to the first to seventh embodiments. The ink composition preferably contains 3 to 50 mass% of (meth)acrylate (A), 20 to 80 mass% of polymerizable compound (b1), and 0 to 70 mass% of polymerizable compound (b2), which are components of E. By containing A, the ink composition has high curability and the surface dryness of the resulting printed surface is good. In addition, by containing b1, the viscosity of the ink composition can be easily adjusted, the pigment dispersibility when a pigment is blended is good, and the ejection stability of the ink composition during printing is high. When a polyfunctional compound is used as b1, the ink composition has sufficient curability even without containing b2, but by containing b2, both the curability of the ink composition and the surface dryness of the resulting printed surface are improved. Furthermore, by combining A, b1, and b2, the viscosity of the ink composition can be suitably adjusted according to the printing method, and the printing clarity of the resulting printed surface is excellent. The ink composition can be applied to a substrate by a conventional method. The viscosity of the ink composition at 25°C is preferably less than 500 mPa·s, and more preferably less than 100 mPa·s from the viewpoint of being able to apply the ink composition to a substrate by an inkjet method. After the ink composition is applied to a substrate, it is cured by irradiation with active energy rays to form a printed surface (ink layer or printed layer). From the viewpoint of being able to express printing characteristics such as the viscosity, pigment dispersibility, curability, ejection stability, and surface dryness and clarity of the resulting printed surface in a well-balanced manner, the ink composition preferably contains 8 to 45% by mass of A, 30 to 80% by mass of b1, and 5 to 65% by mass of b2, and more preferably contains 10 to 40% by mass of A, 40 to 60% by mass of b1, and 10 to 50% by mass of b2.

[0037] The ninth embodiment of the present invention is an ink composition for two-dimensional or three-dimensional modeling (hereinafter, also referred to as a modeling ink composition or modeling ink). The modeling ink composition contains the active energy ray curable composition (E) according to the first to seventh embodiments. The modeling ink composition preferably contains 5 to 60 mass% of (meth)acrylate (A), 15 to 80 mass% of polymerizable compound (b1), and 10 to 80 mass% of polymerizable compound (b2), which are components of E. By containing the above A, the curing shrinkage of the modeling ink composition is low, so modeling precision is good, and the strength and water resistance of the obtained modeled object are good, and in particular, the heat resistance and impact resistance of the modeled object are excellent. By containing b1, the viscosity of the modeling ink composition can be easily adjusted, so that the stability during modeling and modeling precision are high, and by containing b2, the curing property of the modeling ink composition is high, and the strength of the obtained modeled object is high. When b2 contains an oligomer type or polymer type multifunctional compound, both the water resistance and impact resistance of the obtained modeled object are improved. Furthermore, by combining A, b1 and b2, the viscosity of the ink composition for modeling can be suitably adjusted according to the modeling method, and the precision of the resulting modeled object is excellent. The ink composition for modeling is cured by irradiation with active energy rays at the same time as or immediately after being formed into a predetermined shape pattern to form a thin film, and a two-dimensional or three-dimensional object is formed by stacking the thin films. The modeling method is not particularly limited, but examples include a photo-modeling method in which the ink composition is discharged by an inkjet method and cured by irradiation with active energy rays. In this case, from the viewpoint of stable discharge, the viscosity of the ink composition for modeling at 25°C is preferably 1 to 200 mPa·s, and the discharge temperature is preferably in the range of 20 to 100°C. From the viewpoint of enabling the obtained two-dimensional or three-dimensional object to exhibit a good balance between heat resistance, impact resistance, water resistance, high strength, and excellent formation precision, the ink composition for forming preferably contains 5 to 50 mass% of A, 20 to 70 mass% of b1, and 15 to 75 mass% of b2, and more preferably contains 10 to 40 mass% of A, 30 to 60 mass% of b1, and 20 to 60 mass% of b2.

[0038] The tenth embodiment of the present invention is a pressure-sensitive adhesive composition (hereinafter also referred to as pressure-sensitive adhesive). The pressure-sensitive adhesive composition contains the active energy ray-curable composition (E) according to the first to seventh embodiments. The (meth)acrylate (A) and polymerizable compound (B) in the pressure-sensitive adhesive composition can be brought in from E containing A and B, or can be added directly when preparing the pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition preferably contains A in a total content of 2 to 60 mass%, b1 as B in a total content of 5 to 75 mass%, and b2 as B in a total content of 10 to 80 mass%. A contains an amide group and a cyclic substituent, so that the pressure-sensitive adhesive composition has sufficient cohesive strength and adhesive strength, and has good adhesion to various substrates and good stain resistance, and has low cure shrinkage, so that the resulting pressure-sensitive adhesive layer and pressure-sensitive adhesive laminate have excellent durability. Furthermore, by containing b1 and / or b2, the viscosity and curability of the adhesive composition can be easily adjusted according to the purpose, and the transparency of the adhesive composition and the adhesive layer and adhesive laminate obtained by curing the same is good, and in particular, when the adhesive composition contains 5 to 50 mass% of an oligomer type or polymer type multifunctional compound (total of b1 and b2), the adhesive strength and durability of the adhesive layer after curing with active energy rays are high, which is more preferable. On the other hand, by crosslinking the adhesive composition using a crosslinking agent by the following crosslinking methods (1) to (3), an adhesive layer and an adhesive laminate having better stain resistance and durability can be obtained.

[0039] The crosslinking method of the tenth embodiment includes: (1) a method in which a pressure-sensitive adhesive composition contains a (meth)acrylate (A) and / or a polymerizable compound (B) having a reactive functional group (such as a hydroxyl group, an amino group, a carboxyl group, or an oxazoline group), introduces a crosslinking point, further contains a compound (crosslinking agent) having a functional group (such as an isocyanate group or a carboxyl group) that can react with these reactive functional groups, and crosslinks the composition by a crosslinking reaction; (2) a method in which a pressure-sensitive adhesive composition contains a multifunctional compound (monomer type, oligomer type, or polymer type), and crosslinks the composition by irradiation with active energy rays; and (3) a method in which a pressure-sensitive adhesive composition contains a multifunctional compound and A or B capable of introducing a crosslinking point, and crosslinks the composition by irradiation with active energy rays and a crosslinking reaction. Note that (3) is a method in which the crosslinking methods (1) and (2) are appropriately combined. In the present invention, examples of the crosslinking agent include polyisocyanate having two or more isocyanate groups in the molecule, polyepoxy having two or more epoxy groups in the molecule, polyaziridine having two or more aziridine groups in the molecule, polycarboxylic acid having two or more carboxyl groups in the molecule, polyoxazoline having two or more oxazoline groups in the molecule, etc. In the present invention, the crosslinking method in other embodiments is the same.

[0040] The adhesive composition according to the tenth embodiment can be applied to or molded on a separator or a substrate, and then cured by irradiating with active energy rays to form an adhesive layer. When the adhesive composition contains an organic solvent, it may be applied to or molded on a separator or a substrate, irradiated with active energy, and cured while evaporating (drying) the organic solvent. However, it is preferable to heat and dry at a temperature of 60 to 120°C for 1 to 30 minutes, and then perform active energy curing, since this provides a more transparent adhesive layer. The adhesive composition can be applied to a separator or a substrate by a conventionally known method, and for example, a normal coating film forming method such as a spin coat method, a spray coat method, a knife coat method, a dipping method, a gravure roll method, a reverse roll method, a screen printing method, or a bar coater method is used.

[0041] A laminate can be obtained by laminating an adhesive layer made of the adhesive composition according to the tenth embodiment and various substrates. Examples of a method for laminating an adhesive layer and various substrates include a transfer method and a roll-to-roll method. The thickness of the adhesive layer in the laminate is not particularly limited because it varies depending on the application, but is usually 4 to 150 μm, and is appropriately about 20 to 120 μm when used for automobile parts, and about 30 to 100 μm when used for electronic materials or optical parts.

[0042] The substrate may be an organic substrate, an inorganic substrate, or a substrate made of an organic-inorganic composite material having a wide range of polarities from low to high depending on the application, and examples of the substrate include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polycarbonate, ABS resins which are acrylonitrile-butadiene-styrene copolymers, acrylic resins such as polyimide resins, polyamide resins, and polymethyl methacrylate, metals such as steel, stainless steel, copper, and aluminum, and glass, as well as hybrid materials in which silica particles, which are inorganic materials, are dispersed in polyimide, which is an organic material. The applications of the resulting laminates are not particularly limited, and examples thereof include electronic materials, optical components, and automotive components.

[0043] In the adhesive composition according to the tenth embodiment, the (meth)acrylate (A) which is a component has a hydrophobic cyclic substituent that exhibits wettability to low polarity substrates and a hydrophilic amide group that exhibits wettability to high polarity substrates in the molecule, and can provide good adhesion to substrates from low polarity to high polarity. In addition, by expressing a strong cohesive force derived from hydrogen bonds between amide groups in the molecules of A, high adhesive strength and contamination resistance can be provided. Furthermore, since A has a high refractive index, A has good compatibility with the polymerizable compound (B), and the adhesive composition has high transparency and yellowing resistance, the resulting adhesive layer also has high transparency and yellowing resistance, and is suitably used in the optical field, such as an adhesive for optical members and an adhesive sheet. A laminate consisting of an adhesive layer having such characteristics and various substrates can be applied as an adhesive film or adhesive sheet for electronic materials, optical members, and automotive members. When A has different ethylenically unsaturated groups, some of the ethylenically unsaturated bonds can be photocured by irradiation with active energy rays, and then the remaining ethylenically unsaturated bonds can be thermally polymerized by heating. In such a hybrid curing method, after an adhesive layer or adhesive laminate is produced by active energy rays, the crosslinking reaction is further promoted by heating, and peeling, reworking, recycling, etc. can be performed. In addition, by laminating an opaque substrate such as a metal after irradiation with active energy rays and heating it, adhesion using active energy rays to semi-transparent and opaque substrates can be achieved, and an adhesive laminate formed from different materials can also be obtained.

[0044] The eleventh embodiment of the present invention is an adhesive composition (hereinafter also referred to as adhesive). The adhesive composition contains the active energy ray curable composition (E) according to the first to seventh embodiments. In this embodiment, a crosslinking agent may be contained, and crosslinking may be performed by the various crosslinking methods. The adhesive composition, like the pressure-sensitive adhesive composition, contains (meth)acrylate (A) to provide good adhesion to low-polarity to high-polarity substrates, and by combining A with a polymerizable compound (B), various substrates made of organic substrates, inorganic substrates, and organic-inorganic composite materials can be bonded by various curing methods, and the adhesive layer after curing can exhibit high adhesive strength and impact resistance, and can be used as an adhesive composition for homogeneous or heterogeneous materials. Among the various materials such as the resin materials, metal materials, glasses, and hybrid materials described above, two or more of the same type of materials refer to homogeneous materials, and two or more different types of materials refer to heterogeneous materials.

[0045] The (meth)acrylate (A) and polymerizable compound (B) in the adhesive composition can be brought in from the active energy ray composition (E) containing A and B, or can be added directly when preparing the adhesive composition. The adhesive composition preferably has a total content of A of 2 to 65% by mass, a total content of b1 as B of 0 to 75% by mass, and a total content of b2 as B of 5 to 90% by mass. A contains an amide group and a cyclic substituent, so that the adhesive composition has sufficient cohesive strength and adhesion to various substrates, and the adhesive strength of the adhesive layer after curing is high, and the curing shrinkage of the adhesive composition is low, and the impact resistance of the resulting adhesive layer and adhesive laminate is excellent. In addition, the viscosity of the adhesive composition and the content of the monofunctional polymerizable compound and the polyfunctional compound as B can be easily adjusted according to the substrate and curing method used. When the content of the monofunctional polymerizable compound (total of b1 and b2) as B in the adhesive composition is 25 to 60% by mass, it is preferable because the viscosity of the adhesive composition is easily adjusted and the curing shrinkage is easily suppressed. Furthermore, when the total content of the polyfunctional compounds (the sum of b1 and b2) as B is 15 to 60 mass %, the adhesive strength is high while maintaining high impact resistance, which is more preferable.

[0046] In the coating composition (hereinafter also referred to as adhesive) according to the twelfth embodiment, the (meth)acrylate (A) and polymerizable compound (B) of the coating composition can be brought in from the active energy ray composition (E) containing A and B, or can be added directly when preparing the coating composition. The coating composition preferably has a total content of A of 5 to 60 mass%, a total content of b1 as B of 5 to 65 mass%, and a total content of b2 as B of 10 to 80 mass%. Since A contains an amide group and a cyclic substituent, the coating composition has high wettability to various substrates, and the abrasion resistance of the coating film after curing is high. In addition, the curing shrinkage of the coating composition is low, and the surface of the obtained cured coating film does not become uneven, resulting in excellent appearance. In addition, the viscosity of the coating composition and the content of the monofunctional polymerizable compound and the polyfunctional compound as B can be easily adjusted according to the substrate and curing method used. From the viewpoint that the viscosity value of the coating composition can be adjusted widely from low to high viscosity, the content of the monofunctional polymerizable compound (total of b1 and b2) as B is preferably 0 to 60 mass%, and the content of the oligomer type or polymer type polymerizable compound (total of b1 and b2) as B is preferably 5 to 40 mass%. Furthermore, when the content of the polyfunctional compound (total of b1 and b2) as B is 15 to 85 mass%, it is more preferable because the abrasion resistance is high while maintaining an excellent appearance of the cured coating film. Furthermore, the two-step irradiation of UV rays and EB rays as active energy rays does not leave any monomer in the cured coating film, and the appearance of the cured coating film does not change (deteriorate) over time. In particular, when the cyclic substituent of A has an unsaturated bond, the (meth)acrylate group of A and the unsaturated bond of the cyclic substituent can be photocured stepwise by UV rays and EB rays, and the abrasion resistance of the obtained cured coating film is further improved.

[0047] In the sealant composition according to the thirteenth embodiment, the (meth)acrylate (A) and the polymerizable compound (B) in the sealant composition can be brought in from the active energy ray composition (E) containing A and B, or can be added directly when preparing the sealant composition. The sealant composition preferably has a total content of A of 5 to 60 mass%, a total content of b1 as B of 0 to 70 mass%, and a total content of b2 as B of 10 to 70 mass%. A contains an amide group and a cyclic substituent, so that the curing shrinkage of the sealant composition is low, and the heat sealability of the sealant obtained is excellent. In addition, by containing b1 and / or b2, it becomes easy to adjust the viscosity, curing method, and curability of the sealant composition according to the purpose, and the sealant obtained by curing has a high sealing effect, and has good resistance to moist heat yellowing and corrosion, which is preferable. In particular, when the polyfunctional compound of oligomer type or polymer type (total of b1 and b2) is contained in an amount of 2 to 45 mass %, the sealant has low water absorption and high outgas resistance after curing with active energy rays, which is more preferable.

[0048] In the nail cosmetic according to the fourteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the nail cosmetic can be brought in from the active energy ray composition (E) containing A and B, or can be added directly when preparing the nail cosmetic. The nail cosmetic preferably has a total content of A of 1 to 30% by mass, a total content of b1 as B of 10 to 65% by mass, and a total content of b2 as B of 5 to 70% by mass. A contains an amide group and a cyclic substituent, so that the nail cosmetic has low cure shrinkage and the resulting cured film has excellent adhesion and surface hardness. Furthermore, the inclusion of b1 and / or b2 makes it easier to adjust the viscosity and curing method and curability of the nail cosmetic according to the purpose, and the resulting nail cosmetic cured film has high surface gloss, which is more preferable.

[0049] In the decorative coating agent according to the fifteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the decorative coating agent can be brought in from the active energy ray composition (E) containing A and B, or can be added directly when preparing the decorative coating agent. The decorative coating agent preferably has a total content of A of 1 to 50 mass%, a total content of b1 as B of 10 to 60 mass%, and a total content of b2 as B of 15 to 70 mass%. Since A contains an amide group and a cyclic substituent, the curing shrinkage of the decorative coating agent is low, and the resulting decorative coating film has excellent elongation and bending resistance. In addition, the tack resistance and pencil hardness of the resulting decorative coating film can be increased by appropriately adjusting the content of b1 and / or b2. Furthermore, after curing with active energy rays and / or decorative molding such as stretching of the cured film, the residual monomers are thermally polymerized by heat treatment, and in particular, when the cyclic substituent of A has an unsaturated bond, the crosslinking rate of the decorative coating film due to the thermal polymerization of the unsaturated bond increases, further improving the scratch resistance and sunscreen resistance of the coating film.

[0050] In the dental material according to the sixteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the dental material can be brought in from the active energy ray composition (E) containing A and B, or can be added directly when preparing the dental material. The dental material preferably has a total content of A of 0.5 to 50 mass%, a total content of b1 as B of 5 to 70 mass%, and a total content of b2 as B of 10 to 60 mass%. Since A contains an amide group and a cyclic substituent, the dental material has low curing shrinkage, and the obtained dental material cured product has excellent surface smoothness and adhesive strength. In addition, by appropriately adjusting the content of b1 and / or b2, the solubility and dispersibility of the dental material, the curability, and the hardness of the cured product can be increased. Furthermore, after curing with active energy rays, the adhesive strength of the dental material cured product can be further increased by thermal polymerization of the remaining monomer by heat treatment, particularly when the cyclic substituent of A has an unsaturated bond, due to the thermal polymerization of the unsaturated bond.

[0051] The active energy ray curable composition (E) according to the first to seventh embodiments of the present invention may contain various additives other than those described above, if necessary. Examples of additives include thermal polymerization inhibitors, antioxidants, ultraviolet sensitizers, preservatives, phosphate esters and other flame retardants, surfactants, antistatic agents, colorants such as pigments and dyes, fragrances, defoamers, fillers, silane coupling agents, surface tension regulators, plasticizers, surface lubricants, leveling agents, softeners, organic fillers, inorganic fillers, and silica particles. These additives may be used alone or in combination of two or more. The content of these additives is not particularly limited as long as it does not adversely affect the properties of various molded products of E, but is preferably 5% by mass or less based on the total weight of E.

[0052] Various additives other than those described above can be blended into the compositions according to the eighth to sixteenth embodiments of the present invention as necessary. Examples of additives include thermal polymerization inhibitors, antioxidants, ultraviolet sensitizers, preservatives, phosphate esters and other flame retardants, surfactants, antistatic agents, colorants such as pigments and dyes, fragrances, defoamers, fillers, silane coupling agents, surface tension adjusters, plasticizers, surface lubricants, leveling agents, softeners, organic fillers, inorganic fillers, and silica particles. These additives may be used alone or in combination of two or more. The content of these additives is not particularly limited as long as it does not adversely affect the properties of various molded products obtained from the various compositions, but is preferably 30% by weight or less with respect to the total weight of the composition. In addition, water, organic solvents, and mixtures thereof can be used as solvents or diluents as necessary. The content of such solvents is not particularly limited as long as it does not adversely affect the properties of various molded products obtained from the various compositions, but is preferably 95% by weight or less with respect to the total weight of the composition.

[0053] The active energy ray curable composition (E) may further contain a polymerization initiator. In this case, E has improved curability by active energy ray irradiation, and can be suitably used as an active energy ray curable ink composition according to another embodiment of the present invention, a two-dimensional or three-dimensional modeling composition, a pressure-sensitive adhesive composition, a coating composition, a sealant composition, a nail cosmetic, a decorative coating agent, a dental material, a water-resistant coating composition, a coating agent for vehicles, and a coating agent for indoor and / or outdoor building materials.

[0054] In this specification, the active energy ray is defined as an energy ray capable of decomposing a compound (photopolymerization initiator) that generates an active species to generate an active species. Examples of such active energy ray include visible light, ultraviolet light, infrared light, α-ray, β-ray, γ-ray, X-ray, and electron beam (EB). When an electron beam is used as the active energy ray, a photopolymerization initiator may not be used. On the other hand, when ultraviolet light or visible light is used, it is preferable to use a photopolymerization initiator. The active energy ray is preferably irradiated under an inert gas atmosphere such as nitrogen gas or carbon dioxide gas or under an atmosphere with a reduced oxygen concentration, but the active energy ray curable composition (E) according to each embodiment of the present invention and the curable composition containing E for various applications have good curability because of the (meth)acrylate (A) and the polymerizable compound (B), and can be sufficiently cured even under a normal air atmosphere. The irradiation temperature of the active energy ray is preferably 10°C to 200°C, and the irradiation time is preferably 1 second to 60 minutes.

[0055] The photopolymerization initiator may be any substance that generates radicals by irradiation with active energy rays (i.e., photoradical polymerization initiator). For example, benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and anisole methyl ether, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-cyclohexylacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenylketone, acetophenones such as 4-phenoxydichloroacetophenone and 4-t-butyl-dichloroacetophenone, propiophenones such as 2-hydroxy-2-methylpropiophenone and 2-hydroxy-4'-isopropyl-2-methylpropiophenone, benzophenone, and the like. benzophenone, such as benzophenone, methylbenzophenone, p-chlorobenzophenone, and p-dimethylaminobenzophenone; thioxanthones, such as thioxanthone, 2-chlorothioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone; acylphosphine oxides, such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, (bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphenylphosphine oxide; benzyl, dibenzosuberone, and α-acyloxime esters.In addition, commercially available products that can be used include those manufactured by IGM Resins BV under the trade names Omnirad 1116, Omnirad 1173, Omnirad 184, Omnirad 369, Omnirad 500, Omnirad 651, Omnirad 754, Omnirad 819, Omnirad 907, Omnirad 1300, Omnirad 1800, Omnirad 1870, Omnirad 2959, Omnirad 4265, Omnirad TPO, and those manufactured by UCB under the trade name Ubecryl P36. These photopolymerization initiators may be used alone or in combination of two or more kinds.

[0056] The content of the photopolymerization initiator is usually 0.1 to 30% by mass, preferably 0.5 to 20% by mass, and more preferably 0.5 to 3% by mass, based on the total mass of the various curable compositions according to the embodiments of the present invention. Although it depends on the type of photopolymerization initiator, the type of active energy rays, the illuminance, etc., if the content is less than 0.1% by mass, sufficient curability cannot be obtained, and if it exceeds 30% by mass, the performance such as strength of the cured product may be reduced. In this specification, a compound having a functional group with a photopolymerization initiation function and an ethylenically unsaturated group simultaneously in the molecule can be used as a polymerizable photopolymerization initiator. Depending on the number of ethylenically unsaturated groups contained therein, it is called a monofunctional polymerizable photopolymerization initiator or a polyfunctional polymerizable photopolymerization initiator. When a polymerizable photopolymerization initiator is contained, it may be used alone or may not be used in combination with a commercially available photopolymerization initiator.

[0057] The active energy ray curable composition (E) may further contain a non-polymerizable oligomer and / or a non-polymerizable polymer. In this specification, those having an ethylenically unsaturated group in the molecule and having a weight average molecular weight (Mw) of 1,000 or more and less than 10,000 are classified as non-polymerizable oligomers, and those having Mw of 10,000 or more are classified as non-polymerizable polymers. Examples of the non-polymerizable oligomers and non-polymerizable polymers include thermoplastic resins, rosin-based resins, and mixtures thereof. Examples of the thermoplastic resins include (meth)acrylic resins, cyclic polyolefin resins, cellulose resins, polyester resins, polyurethane resins, polysulfonic acid resins, ABS resins, polycarbonate resins, polyamide resins, and polyimide resins. Examples of the rosin-based resins include natural rosins such as gum rosin, and modified rosin resins such as hydrogenated rosins obtained by modifying natural rosin, disproportionated rosin, rosin-modified phenolic resins, maleic acid-modified rosin resins, maleic rosin, and esterified gum. These non-polymerizable oligomers and / or non-polymerizable polymers may be used alone or in combination of two or more kinds.

[0058] The total content of the non-polymerizable oligomer and the non-polymerizable polymer is usually 0.1 to 20 mass%, preferably 0.5 to 15 mass%, and more preferably 1 to 10 mass% based on the total mass of the various curable compositions according to the embodiments of the present invention. By containing the non-polymerizable oligomer and the non-polymerizable polymer, the curing shrinkage rate of the active energy ray curable composition (E) and the curable composition containing it for each application can be reduced, the viscosity can be adjusted, the wettability and adhesion to the substrate can be improved, and the surface hardness, tensile strength, water resistance, heat resistance, impact resistance durability, abrasion resistance, etc. of the obtained cured film and cured product can be improved, and the composition can be suitably used depending on the purpose. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The abbreviations of the components described in the examples and comparative examples are as follows. In the following, "parts" and "%" are all based on mass unless otherwise specified. (1) (Meth)acrylate (A) The (meth)acrylates (A-1) to (A-15) used in the examples are shown in Table 1.

[0060] (2) Polymerizable compound (B) <Polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms> b1-1: Dimethylacrylamide (registered trademark "Kohshylmer", "DMAA") b1-2: Diethylacrylamide (registered trademark "Kohshylmer", "DEAA") b1-3: Isopropylacrylamide (registered trademark "Kohshylmer", "NIPAM") b1-4: N-(2-hydroxyethyl)acrylamide (registered trademark "Kohshylmer", "HEAA") b1-5: N-[3-(dimethylamino)]propylacrylamide (registered trademark "Kohshylmer", "DMAPAA") b1-6: Diacetone acrylamide (registered trademark "Kohshylmer") B1-7: 2-Ethylhexyl acrylate B1-8: 2-(2-ethoxyethoxy)ethyl acrylate B1-9: 4-hydroxybutyl acrylate B1-10: Pentaerythritol triacrylate B1-11: Dipentaerythritol hexaacrylate B1-12: 1,6-Hexanediol diacrylate B1-13: Tripropylene glycol diacrylate <Polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms> b2-1: N-cyclohexyl acrylamide (registered trademark "Kohshylmer") b2-2: N-acryloylmorpholine (registered trademark "Kohshylmer", "ACMO") b2-3: N-phenylacrylamide (registered trademark "Kohshylmer") b2-4: Dopamine acrylamide (registered trademark "Kohshylmer") b2-5: 3-acrylamidophenylboronic acid (registered trademark "Kohshylmer") B2-6: tert-butylcyclohexyl acrylate (registered trademark "Kohshylmer") B2-7: Isobornyl acrylate B2-8: Tetrahydrofurfuryl acrylate B2-9: Tricyclodecane dimethanol diacrylate b2-10: UV-3000B: Bifunctional urethane acrylate (Shiko, manufactured by Mitsubishi Chemical Corporation) b2-11: UV-6640B: Bifunctional urethane acrylate (Shiko, manufactured by Mitsubishi Chemical Corporation) b2-12: Quick Cure 7100: UV-curable urethane oligomer (registered trademark "Quick Cure", manufactured by KJ Chemicals) b2-13: Quick Cure 8100: UV-curable urethane oligomer (registered trademark "Quick Cure", manufactured by KJ Chemicals) <Polymerizable compound (b3) (excluding A, b1 and b2)> B3-1: glycidyl methacrylate B3-2: 2-vinyl-2-oxazoline B3-3: Acrylonitrile B3-4: Acrylic acid

[0061] (3) Photopolymerization initiator (C) C-1: Omnirad 184 (photopolymerization initiator, manufactured by IGM Resins BV) C-2: Omnirad 1173 (photopolymerization initiator, manufactured by IGM Resins BV) C-3: Omnirad TPO (photopolymerization initiator, manufactured by IGM Resins BV)

[0062] (4)Other D-1: Hydrogenated rosin (non-polymerizable polymer, Tackyfire KE-359, manufactured by Arakawa Chemical Industries) D-2: Acrylic resin (non-polymerizable polymer, VS-1057, Seiko PMC) D-3: Blenmer (non-polymerizable oligomer, PME-4000, NOF Corp.) D-4: BYK-331 (leveling agent, polyether-modified polydimethylsiloxane, manufactured by BYK Chemie) D-5: Pigment dispersion (NX-061 Green, manufactured by Dainichiseika Color & Chemicals Co., Ltd.) D-6: Hexamethylene diisocyanate D-7: Inorganic filler (titanium oxide) (5) Base material PP: Polypropylene plate and film PC: Polycarbonate plate and film PMMA: Polymethyl methacrylate plates and films PET: Easy-to-adhere polyethylene terephthalate plate and film ABS: Acrylonitrile-butadiene-styrene copolymer synthetic resin board SPCC: Cold rolled steel plate SUS: Stainless steel plate Al: Aluminum plate Cu: copper plate PO: Polyolefin sheet PVC: Polyvinyl chloride board HDF: Wood board (high density fiberboard)

[0063] <Preparation and Evaluation of Active Energy Ray-Curable Composition> Examples 1 to 16 and Comparative Examples 1 to 4 The (meth)acrylate (A), polymerizable compound (B) (b1 having a chain-like substituent and b2 having a cyclic substituent), photopolymerization initiator (C) and other components used in this embodiment were weighed out in the proportions shown in Table 2 and mixed uniformly at room temperature to prepare curable compositions of the Examples and Comparative Examples. The transparency (compatibility), curability and cure shrinkage resistance of the obtained curable compositions were evaluated by the following methods, and the results are shown in Table 2. In addition, the water resistance of the cured products obtained in each Example and Comparative Example was evaluated by the following method, and the results are shown in Table 2.

[0064] <Evaluation of transparency (compatibility) of curable composition> The state of the active energy ray-curable compositions prepared in each of the Examples and Comparative Examples was visually observed, and the transparency (compatibility) was evaluated into four stages. ◎: High transparency, no turbidity or separation observed. Good: High transparency, but slight turbidity observed. △: No phase separation, but turbidity. ×: Turbidity or phase separation is observed.

[0065] <Curability evaluation (365nm, 385nm and 405nm)> The active energy ray curable compositions prepared in each Example and Comparative Example were applied to the easy-adhesion treated surface of a 100 μm-thick PET film ("Cosmoshine A-4100", Toyobo) using a bar coater to a film thickness of 20 μm, and then the coating film was cured by irradiating it with ultraviolet light. The cumulative light amount at which the tack disappeared when touching the cured product was determined, and the curability was evaluated in four stages. The following three types of ultraviolet irradiating lamps 1) to 3) were used. The lower the cumulative light amount required until the tack disappeared (complete curing), the higher the curability. 1) UV LED lamp: Wavelength 365 nm, output 100 mW / cm 2 2) UV LED lamp: Wavelength 385 nm, output 100 mW / cm 2 3) UV LED lamp: Wavelength 405 nm, output 100 mW / cm 2 ◎: Accumulated light intensity 200mJ / cm 2 Tack disappears below ○: Accumulated light intensity 200mJ / cm 2 More than 500mJ / cm 2 Tack disappears below △: Accumulated light intensity 500mJ / cm 2 More than 1000mJ / cm 2 Tack disappears below ×: Accumulated light intensity 1000mJ / cm 2 The tack will disappear (including cases where the tack does not disappear)

[0066] <Evaluation of resistance to curing shrinkage> A silicone spacer (30 mm long x 15 mm wide x 1 mm thick) was placed on a glass plate (50 mm long x 50 mm wide x 5 mm thick), and the active energy ray-curable composition prepared in each Example and Comparative Example was poured into the spacer, followed by UV irradiation (apparatus: inverter-type conveyor device ECS-4011GX manufactured by I-Graphics, metal halide lamp: M04-L41 manufactured by I-Graphics, UV illuminance: 700 mW / cm 2 , Accumulated light intensity: 1000mJ / cm 2 ) to prepare a cured sheet. The cure shrinkage was calculated from the change in density before and after curing of the active energy ray curable composition according to JIS K5600 2-4, as shown in the following formula (1). The density of the curable composition before and after curing was measured using an electronic densimeter (MDS-300 manufactured by Alpha Mirage Co., Ltd.) according to JIS K7112. The density of the prepared cured sheet was taken as the density of the curable composition after curing, and the following evaluation was performed based on the cure shrinkage. (Cure shrinkage rate) = (Ds-Dl) / Dl x 100 Formula (1) (In the formula, Ds is the density of the curable composition after curing, and Dl is the density of the curable composition before curing.) ⊚: The cure shrinkage rate is 3% or less. ◯: The cure shrinkage rate exceeds 3% but is 5% or less. △: The cure shrinkage rate exceeds 5% but is 8% or less. ×: The cure shrinkage rate exceeds 8%.

[0067] <Water resistance evaluation of cured product> A cured sheet was prepared in the same manner as in the evaluation of cure shrinkage resistance, and the resulting sheet was cut into 3 cm squares, dried under vacuum at 60°C for 24 hours, and accurately weighed as a dry sheet, which was used as the weight of the cured product in its dry state. The dried sheet was immersed in deionized water at 30°C, and after 24 and 48 hours, the weight was weighed immediately after removing it from the deionized water to confirm that the sheet had reached a saturated water absorption state, which was used as the weight of the cured product in its saturated water absorption state. The saturated water absorption rate was calculated according to the following formula, and the water resistance of the cured product was evaluated in four stages as follows. Saturated water absorption rate (%) = (weight at saturation - weight at dry state) / weight at dry state x 100% ◎: Saturated water absorption is 8% or less. ○: The saturated water absorption rate is more than 8% but is 10% or less. △: The saturated water absorption rate is more than 10% but is 20% or less. ×: The saturated water absorption rate exceeds 20%.

[0068] As is clear from the results in Table 2, the active energy ray curable composition of each Example has a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule, and a polymerizable compound (b1) containing a chain-like substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) containing a cyclic substituent having 3 to 20 carbon atoms, and therefore has good transparency (compatibility), high curability for light rays of 365 nm, 385 nm and 405 nm, and low cure shrinkage upon curing. It was also confirmed that the obtained cured product has excellent water resistance. On the other hand, in Comparative Examples 1 to 4, since the (meth)acrylate (A) and the polymerizable compound (B) (b1 and / or b2) were not simultaneously contained, the transparency, curability and cure shrinkage resistance of the curable composition were not all satisfactory. In addition, the cured product of the Comparative Example had poor water resistance. It is considered that such different physical properties between the Examples and the Comparative Examples are due to the interaction between A and B contained in the active energy ray curable composition of the present invention, as described above.

[0069] <Preparation and Evaluation of Active Energy Ray-Curable Ink Composition> Examples 17 to 22 and Comparative Examples 5 to 8 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 3, and mixed uniformly at room temperature to prepare ink compositions of Examples and Comparative Examples. Using the prepared ink compositions, viscosity measurements were performed by the following method, and pigment dispersibility evaluation was performed when a pigment dispersion liquid was contained. The active energy ray curability of the ink composition and the surface drying property of the obtained cured film were evaluated, and further inkjet printing was performed, and the ink discharge stability and the clarity of the printed matter were evaluated as printability. The results of these evaluations are summarized in Table 3. Note that Example 18 is an example in which curing is performed by irradiating with an electron beam (EB) instead of ultraviolet rays. As an EB irradiation device, a Curetron EBC-200-AA3 manufactured by Nissin High Voltage Co., Ltd. was used (accelerating voltage: 200 kV, exposure dose 20 kGy).

[0070] <Viscosity measurement and evaluation> The viscosity of the ink composition was measured in accordance with JIS K5600-2-3 using a cone-plate viscometer (RE550 viscometer manufactured by Toki Sangyo Co., Ltd.) As an ink composition for inkjet printing, the viscosity was evaluated into the following four levels. ◎: 5 or more, less than 100 mPa s ○: 100 or more, less than 500 mPa s △: 500 or more, less than 2000 mPa s ×:2000mPa·s or more

[0071] <Evaluation of pigment dispersibility> The prepared ink compositions were visually observed for pigment aggregation and precipitation immediately after preparation and after being left to stand at room temperature for 2 months, and the pigment dispersibility was evaluated into the following 4 levels. ⊚: No pigment aggregation or precipitation was observed immediately after preparation or after leaving the mixture to stand for 2 months. ◯: No precipitation was observed immediately after preparation, but slight precipitation of pigment was observed after leaving it to stand for 2 months. △: Slight pigment aggregation and precipitation was observed immediately after preparation, but after leaving the mixture for 2 months, aggregation and precipitation of the pigment was clearly observed. ×: Pigment aggregation and precipitation were clearly observed even immediately after preparation.

[0072] Method for producing printed matter by irradiation with active energy rays The obtained ink composition was applied to a 100 μm thick PET film using a bar coater (RDS12) (film thickness after drying: 10 μm), and cured by exposure to ultraviolet light (inverter type conveyor device ECS-4011GX, metahalide lamp M04-L41, manufactured by iGraphics Co., Ltd.) to produce a printed matter.

[0073] <Evaluation of Curability of Ink Composition> When a printed matter was produced by the above method, the integrated amount of light until the ink composition was completely cured (until it became non-sticky) was measured, and the curability was evaluated. ◎: 1000mJ / cm 2 Completely cured in less than ○: 1000 or more, 2000mJ / cm 2 Completely cured in less than △:2000 or more, 5000mJ / cm 2 Completely cured in less than ×: 5000mJ / cm until complete curing 2 More than this is required

[0074] <Surface drying evaluation> The print produced by the above method was left to stand for 5 minutes in an environment with a room temperature of 23°C and a relative humidity of 50%, and then a sheet of high-quality paper was placed on the printed surface and a load of 1 kg / cm was applied. 2 A load of this value was applied for one minute, and the degree of ink transfer to the paper was evaluated. ⊚: The ink was dry and not transferred to the paper at all. ○: The ink was dried and there was a small amount of transfer onto the paper. △: The ink was almost dry and was transferred to the paper. ×: The ink was barely dried and a large amount was transferred to the paper.

[0075] <Inkjet printing and printability evaluation> The prepared ink composition was filled into a commercially available inkjet printer (LuxelJet UV350GTW manufactured by Fujifilm Corporation), and a solid image was printed on coated paper. The printability of the ink was evaluated by the following method.

[0076] <Evaluation of ejection stability> The print state of the printed matter obtained by inkjet printing was evaluated visually. ⊚: No missing nozzles, good printing. Good: There is a slight nozzle dropout. △: Nozzle missing occurs over a wide area. ×: Non-ejection occurred.

[0077] <Clarity evaluation> The image clarity of the ink-jet printed matter obtained from the ink composition containing the pigment was visually observed. ⊚: No ink bleeding was observed and the image was clear. A: There was almost no ink bleeding and the image was good. △: Some ink bleeding was observed. ×: Significant ink bleeding was observed.

[0078] The viscosity of the active energy ray curable ink composition of the present invention can be adjusted arbitrarily according to various printing methods such as inkjet printing, offset printing, screen printing, and flexographic printing. As is clear from the results in Table 3, the viscosity can be adjusted to be low as an ink composition for inkjet printing, and when a pigment is blended, the ink composition has high pigment dispersibility. The reason for such results is that the compatibility of the (meth)acrylate (A) and the polymerizable compound (B) contained in the examples is extremely good, and the polymerizable compound (b1) having a chain substituent and the polymerizable compound (b2) having a cyclic substituent are available in a wide variety of varieties ranging from low viscosity to high viscosity, and are easily combined with other components such as pigment dispersants. In addition, by combining A with b1 and / or b2, the ink composition of the examples had high curability, the surface drying property of the obtained cured film was good, and the clarity of the printed matter, which is the printability of the inkjet ink composition, was good. On the other hand, the ink compositions of the comparative examples were not satisfactory in viscosity, pigment dispersibility, curability, surface drying property, and inkjet printability.

[0079] <Preparation and evaluation of active energy ray curable ink composition for three-dimensional modeling> Examples 23 to 29 and Comparative Examples 9 and 10 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 4 and mixed uniformly at room temperature to prepare ink compositions for three-dimensional modeling of Examples and Comparative Examples. Using the ink compositions for three-dimensional modeling, three-dimensional objects were produced by the following method, and the strength, heat resistance and modeling accuracy of the obtained cured objects were evaluated. The evaluation results are shown in Table 4.

[0080] <Strength evaluation> A 75 μm-thick heavy release PET film (Toyobo Co., Ltd., polyester film E7001) was attached to a horizontally placed glass plate, a 1 mm-thick spacer punched into a No. 2 dumbbell shape conforming to JIS K6251 was placed, and the ink composition for three-dimensional modeling obtained in each Example and Comparative Example was filled inside the spacer. A 50 μm-thick light release PET film (Toyobo Co., Ltd., polyester film E7002) was then placed on top of the spacer, and ultraviolet light was irradiated from both sides (device: I-Graphics Co., Ltd., inverter conveyor device ECS-4011GX, metal halide lamp: I-Graphics Co., Ltd. M04-L41, ultraviolet light illuminance 200 mW / cm). 2 , cumulative light intensity 1000mJ / cm 2 ) to cure the ink composition for three-dimensional modeling. Thereafter, the release PET films on both sides were removed to obtain test pieces of the cured product for the examples and the cured product for the comparative examples. In accordance with JIS K7161, the tensile strength was measured using a bench-top precision universal testing machine (Autograph AGS-X manufactured by Shimadzu Corporation) at a temperature of 25°C, a tensile speed of 10 mm / min, and a chuck distance of 50 mm, and the strength was evaluated according to the following criteria. ◎: Tensile strength 40MPa or more ○: Tensile strength 30MPa or more and less than 40MPa △: Tensile strength 20MPa or more and less than 30MPa ×: Tensile strength less than 20 MPa

[0081] <Heat resistance evaluation> Cured products were prepared in the same manner as the test pieces for the tensile tests, and the glass transition temperature (Tg) of the cured products was measured using a differential scanning calorimeter (DSC-60plus, manufactured by Shimadzu Corporation). The following evaluations were made regarding heat resistance based on the measured glass transition temperature (Tg) of the cured products. ○: Cured product Tg 80℃ or higher △: Cured product Tg 40℃ or higher but lower than 80℃ ×: Cured product Tg below 40°C

[0082] <Impact resistance evaluation> A 75 μm-thick heavy release PET film (Toyobo Co., Ltd., polyester film E7001) was attached to a horizontally placed glass plate, a 4 mm-thick spacer with an internal dimension of 10 × 80 mm was placed, and the ink composition for three-dimensional modeling obtained in each of the Examples and Comparative Examples was filled to a thickness of 4 mm inside the spacer. A 50 μm-thick light release PET film (Toyobo Co., Ltd., polyester film E7002) was then placed on top of the ink composition, and ultraviolet light was irradiated from both sides (device: I-Graphics Co., Ltd., inverter conveyor device ECS-4011GX, metal halide lamp: I-Graphics Co., Ltd. M04-L41, ultraviolet light illuminance 200 mW / cm). 2 , cumulative light intensity 1,000mJ / cm 2 ) to cure the ink composition. Thereafter, the release PET films on both sides were removed, and the ink composition was further irradiated with ultraviolet light at a predetermined integrated light amount (apparatus: ITEC System Co., Ltd., tabletop batch-type UV-LED curing apparatus MUVBA-0.3×0.3×0.5, wavelength 405 nm, illuminance (UV-V) 50 mW / cm 2 , cumulative light intensity 5,000mJ / cm 2 ), and post-curing was performed to completely cure the material. The obtained cured material was then used as a test piece to measure Izod impact strength (with notch) in accordance with JIS K-7110, and the impact resistance was evaluated as follows. An Izod-Charpy impact tester "Model No. 195-R" manufactured by Yasuda Seiki Seisakusho Co., Ltd. was used. The higher the impact strength, the higher the impact resistance. ◎:40J / m or more ○: 30J / m or more but less than 40J / m △: 20J / m or more and less than 30J / m ×: Less than 20 J / m

[0083] <Water resistance evaluation> Using a spacer with a thickness of 10 mm and an internal dimension of 10 cm x 1 cm, a cured test piece for evaluating water resistance, 10 cm long x 1 cm wide x 1 mm thick, was prepared in the same manner as in the strength evaluation and test piece preparation. The weight of the obtained test piece was measured immediately after molding, and then it was immersed in a beaker containing 100 ml of water, and the weight after immersion was measured one day later. The weight before immersion and the weight after immersion were substituted into the following formula to measure the water absorption rate, and the water resistance was evaluated according to the following criteria. The lower the water absorption rate, the higher the water resistance. ◎: Water absorption rate is less than 2% ○: Water absorption rate is 2% or more and less than 2.5% △: Water absorption rate is 2.5% or more and less than 3% ×: Water absorption rate is 3% or more

[0084] <Modeling accuracy evaluation> A 75 μm-thick heavy-release PET film (Toyobo Co., Ltd., polyester film E7001) was attached to a horizontally placed glass plate, a 10 mm-thick spacer with an internal dimension of 10 × 10 mm was placed, and the ink composition for three-dimensional modeling obtained in each of the Examples and Comparative Examples was filled to a thickness of 1 mm inside the spacer. The surface was then smoothed by keeping the temperature at 60°C for 30 seconds, and then irradiated with ultraviolet light (apparatus: Eye Graphics Co., Ltd., inverter conveyor device ECS-4011GX, metal halide lamp: Eye Graphics Co., Ltd. M04-L41, ultraviolet illuminance 200 mW / cm 2 ) and the ink composition for three-dimensional modeling was cured. Thereafter, the ink composition for three-dimensional modeling was filled to a thickness of 1 mm, and the curing process was repeated 10 times in total to obtain a cured product of 10 x 10 x 10 mm. The height of the obtained cured product was measured. In addition, the side surface of the obtained cured product was visually observed. These results were combined and the modeling accuracy was evaluated according to the following criteria. ◎: Height is less than 10 mm ± 0.1 mm and the sides are smooth. ○: Height is 10mm ±0.1mm or more but less than ±0.2mm, or there are slight irregularities on the side. △: Height is 10mm ±0.2mm or more but less than ±0.3mm, or there are slight irregularities on the sides. ×: Height is 10mm±0.3mm or more, or there are obvious irregularities on the side.

[0085] As is clear from the results in Table 4, the ink compositions for three-dimensional modeling of the Examples have excellent resistance to cure shrinkage, and by using them, it is possible to obtain three-dimensional photo-modeled objects with high modeling accuracy, and the heat resistance and impact resistance of the obtained objects are very good, and sufficient strength and water resistance can be obtained by adjusting the type and content of the (meth)acrylate (A) and the polymerizable compound (B). Objects with such good properties were not obtained from the compositions of the Comparative Examples.

[0086] <Preparation and Evaluation of Pressure-Sensitive Adhesive Composition> Examples 30 to 35 and Comparative Examples 11 and 12 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 5, and uniformly mixed at room temperature to prepare adhesive compositions of Examples and Comparative Examples. Using the adhesive composition, an adhesive layer and an adhesive sheet were produced by the following method, and the curability of the adhesive composition, adhesion to various substrates, and the transparency, adhesive strength, stain resistance (reworkability), durability and yellowing resistance of the obtained adhesive layer were evaluated, and the results are shown in Table 5. In addition, in Examples 30 and 33, the adhesive sheet after active energy ray curing was placed in a thermostatic chamber at 80°C, and the crosslinking reaction was completed by aging for 48 hours, and then various physical properties of the adhesive layer were evaluated.

[0087] <Adhesive curing evaluation> A 75 μm-thick heavy release PET film (Toyobo Co., Ltd., polyester film E7001) was attached to a horizontally placed glass plate, a 1 mm-thick spacer with an internal dimension of 60 mm×100 mm was placed, and the active energy ray-curable pressure-sensitive adhesive composition prepared in the Examples and Comparative Examples was filled inside the spacer. A 50 μm-thick light release PET film (Toyobo Co., Ltd., polyester film E7002) was then placed on top of the active energy ray-curable pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition was then measured at a wavelength of 385 nm and an output of 100 mW / cm.2 The UV LED lamp has an integrated light output of 3000mJ / cm 2 The adhesive composition was cured by irradiating the adhesive composition so that the release PET films on both sides were then removed, and the cured product (adhesive layer) was touched and evaluated for curability into three stages. ◯: A cured product that was able to maintain its shape was obtained, and the cured product was tacky when touched, but no liquid uncured product was attached. Δ: A cured product that was able to maintain its shape was obtained, and the cured product was tacky when touched, but some liquid uncured material was attached. ×: Curing was insufficient, a cured product capable of maintaining its shape was not obtained, and a large amount of adherent liquid residue was observed.

[0088] <Preparation of adhesive sheets and evaluation of adhesion> The active energy ray-curable adhesive composition prepared in the same manner as above was applied onto various plate-shaped substrates (substrates), and the substrates were laminated using a tabletop roll laminator (RSL-382S manufactured by Royal Sovereign) with a light release separator (silicone-coated PET film) to avoid trapping air bubbles, so that the adhesive layer had a thickness of 5 μm. The substrates were then irradiated with ultraviolet light (apparatus: inverter-type conveyor device ECS-4011GX manufactured by I-Graphics, metal halide lamp: M04-L41 manufactured by I-Graphics, ultraviolet irradiance: 700 mW / cm 2 , Accumulated light intensity: 5000mJ / cm 2 ) was then applied. The light release separator was then peeled off to obtain an adhesive sheet consisting of an adhesive layer and a substrate. Using the obtained adhesive sheet, 100 1 mm squares were created in accordance with JIS K 5600, cellophane tape was attached, and the tape was peeled off in one go. The number of squares with adhesive layer remaining on the substrate side was counted, and adhesion was evaluated according to the following criteria. ◎: No peeling out of 100 pieces. ○: 95 to 99 pieces, no peeling. △: 70 to 94 pieces, no peeling. ×: 0 to 69 pieces, no peeling.

[0089] <Adhesive strength evaluation> The adhesive layer was transferred to various film- or plate-shaped substrates under conditions of 23°C and 50% relative humidity, and pressure-applied by rolling a 2 kg pressure roller back and forth twice, and left in the same atmosphere for 30 minutes. After that, the 180° peel strength (N / 25mm) was measured at a peel speed of 300mm / min using a tensile tester (Tensilon RTA-100, manufactured by ORIENTEC) in accordance with JIS Z0237. ◎:30(N / 25mm) or more ○: 15 (N / 25mm) or more, less than 30 (N / 25mm) △: 8 (N / 25mm) or more, less than 15 (N / 25mm) ×: Less than 8 (N / 25mm)

[0090] <Transparency evaluation of adhesive layer> The total light transmittance of the glass substrate was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., NDH-2000) in accordance with JIS K 7105. The adhesive layer was transferred to a glass substrate under conditions of a temperature of 23°C and a relative humidity of 50%, and the total light transmittance of the glass substrate and the adhesive layer was measured. Thereafter, the transmittance of the glass plate was subtracted to calculate the transmittance of the adhesive layer itself, and the transparency was evaluated in four stages as follows. ◎: Transmittance is 90% or more ○: Transmittance is 85% or more and less than 90% △: Transmittance is 50% or more and less than 85% ×: Transmittance is less than 50%

[0091] <Contamination resistance (reworkability) evaluation> An adhesive sheet was prepared in the same manner as in the measurement of adhesive strength described above, and after leaving it at 80°C for 24 hours, the surface of the base film was visually inspected for contamination (remaining adhesive layer (glue)) after peeling off the adhesive layer. ◎: No contamination (no adhesive residue). ○: There is very little contamination. △: Slight contamination. ×: Contamination occurred (glue residue remained).

[0092] <Yellowing resistance evaluation> An adhesive sheet was prepared in the same manner as in the measurement of adhesive strength described above, and set in a xenon fade meter (SC-700-WA: manufactured by Suga Test Instruments Co., Ltd.) and measured at 70 mW / cm 2 After irradiation with ultraviolet light of intensity of 100 nm for 120 hours, the discoloration of the adhesive layer on the adhesive sheet was visually observed. ⊚: No yellowing was observed with the naked eye. ○: Yellowing is very slight and visible. △: Yellowing is visually confirmed. ×: Obvious yellowing is visually observed.

[0093] <Durability evaluation> Adhesive sheets were prepared in the same manner as in the measurement of adhesive strength described above, and were then held for 100 hours under conditions of a temperature of 85°C and a relative humidity of 85%, after which the adhesive layer was visually observed and evaluated for the presence or absence of lifting, peeling, air bubbles, or cloudiness. ◎: Transparent, no floating, peeling or air bubbles. ○: There is very little cloudiness, but no lifting, peeling, or air bubbles. △: Slight cloudiness, lifting, peeling, or bubbles. ×: Severe cloudiness, lifting, peeling, or bubbles.

[0094] As is clear from the results in Table 5, the active energy ray curable adhesive composition of the examples had high curability, and the adhesive layer obtained by curing it had high transparency and good adhesion and adhesion (adhesive strength) to various materials. In particular, the cured product (adhesive layer) obtained from the active energy ray curable adhesive composition of the present invention contains (meth)acrylate (A) having both an amide group and a cyclic substituent as a constituent, so that the contamination resistance when the cured product is peeled off from the substrate, as well as the yellowing resistance and durability of the cured product were good. On the other hand, it was found that the curing property, transparency, adhesion and adhesion to various materials were all low, and the contamination resistance, yellowing resistance and durability of the cured product were all low in the composition of the comparative example. In addition, the adhesive strength between the obtained adhesive layer and various substrates was high due to the combined use of a crosslinking reaction. Such good characteristics were not obtained in the composition of the comparative example and the cured product.

[0095] <Preparation and evaluation of adhesive composition> Examples 36 to 41 and Comparative Examples 13 and 14 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed out in the proportions shown in Table 6 and mixed uniformly at room temperature to prepare adhesive compositions of Examples and Comparative Examples. The adhesive compositions were used to bond the same or different plate-like substrates by the following method, adhesive test pieces were prepared, and the adhesive strength and impact resistance were evaluated. The results are shown in Table 6.

[0096] Two sheets of the same or different plate-shaped substrates measuring 100 mm long x 25 mm wide x 1 mm thick were used, and the adhesive composition was uniformly applied to any one of the sheets. When the adhesive composition contained a solvent, a larger amount of the mixture was applied so that the thickness after drying was approximately the same as when no solvent was used, and the mixture was dried at 90°C for 2 minutes. Then, in accordance with JIS K 6850, the other plate-shaped substrate was placed on the applied adhesive composition, and the two were laminated so that the overlapping area was 12.5 mm long x 25 mm wide, and the thickness of the adhesive layer was adjusted to 100 μm using a spacer to prepare a laminated test piece. Then, UV (ultraviolet ray irradiation device: Inverter type conveyor device ECS-4011GX manufactured by I-Graphics, metal halide lamp: M04-L41 manufactured by I-Graphics, ultraviolet ray illuminance: 700 mW / cm) was applied from the top surface of the laminated transparent or translucent substrate. 2 , Accumulated light intensity: 5000mJ / cm 2 ) or EB (EB irradiation device: Curetron EBC-200-AA3 manufactured by Nissin High Voltage Co., Ltd., accelerating voltage: 200 kV, exposure dose: 20 kGy). In the examples in which the curing method in Table 6 is described as UV or EB, the test pieces irradiated with UV rays and EB rays, respectively, were used as the adhesive test pieces. In the examples in which the curing method is described as UV heat, the test pieces irradiated with UV rays were further heated at 80°C for 48 hours, and the obtained test pieces were used as the adhesive test pieces.

[0097] <Adhesion strength evaluation> The tensile shear strength of the obtained adhesive test piece was measured at a tensile speed of 10 mm / min using a Tensilon RTA-100 tester (manufactured by ORIENTEC Co., Ltd.) in accordance with JIS K 6850. Note that the higher the tensile shear strength, the higher the adhesive strength. ◎: The tensile shear strength is 20 MPa or more. ◯: The tensile shear strength is 15 MPa or more and less than 20 MPa. △: The tensile shear strength is 10 MPa or more and less than 15 MPa. ×: The tensile shear strength is less than 10 MPa.

[0098] <Impact resistance evaluation> Using the adhesive test pieces obtained in the same manner as above, the impact peel adhesive strength was measured in accordance with JIS K 6855 using an impact tester No. 511 (manufactured by Mize Testing Instruments Co., Ltd.) Note that the higher the impact peel adhesive strength, the higher the impact resistance. ◎: Impact peel adhesive strength is 20KJ / m2 or more. ◯: Impact peel adhesive strength is 15 KJ / m2 or more and less than 20 KJ / m2. △: Impact peel adhesive strength is 10KJ / m2 or more and less than 15KJ / m2. ×: Impact peel adhesive strength is less than 10 KJ / m2.

[0099] As is clear from the results in Table 6, the active energy ray curable adhesive composition of the examples can be easily cured by ultraviolet (UV) or electron beam (EB), and a laminate with an adhesive layer having high adhesive strength and impact resistance can be obtained. By further heating after UV or EB irradiation, the thermal curing continues and is applicable to adhesion of opaque substrates and different materials. In particular, when the cyclic substituent of the (meth)acrylate (A) has an unsaturated bond, photopolymerization by active energy rays proceeds at a high speed, so that the unsaturated bond of the cyclic substituent is likely to remain, and the unsaturated bond of the cyclic substituent can be completely polymerized by the subsequent thermal polymerization, and the adhesive strength and impact resistance were further improved. Such good characteristics were not obtained in the compositions and cured products of the comparative examples.

[0100] <Preparation and evaluation of coating compositions> Examples 42 to 47 and Comparative Examples 15 and 16 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 7 and mixed uniformly at room temperature to prepare coating compositions of Examples and Comparative Examples. The coating compositions were used to coat various substrates, and the wettability of the coating composition to the various substrates was evaluated. In addition, the coating composition was applied to an ABS plate, and cured with UV, EB, or UV and then with EB to evaluate the curability of the coating composition and the abrasion resistance of the resulting cured coating film. The results are shown in Table 7.

[0101] <Wettability evaluation> The resulting coating compositions were applied to various substrates using a bar coater (RDS 3), and the degree of repelling of the coating film was visually observed, and the wettability was evaluated according to the following four levels. ⊚: No repelling and a uniform coating film. ◯: There is very little repelling, but the coating is almost uniform. Δ: There is some repelling, but overall the coating is fairly uniform. ×: There is a lot of repelling and the coating film is non-uniform.

[0102] <Appearance evaluation of cured coating film> The obtained various coating compositions were applied to a 3 mm thick ABS resin plate using a bar coater (RDS 6) so that the film thickness after curing was 25 μm. The resin plate was irradiated with UV (ultraviolet ray irradiation device: inverter type conveyor device ECS-4011GX manufactured by I-Graphics, metal halide lamp: M04-L41 manufactured by I-Graphics, ultraviolet ray illuminance: 700 mW / cm 2 , Accumulated light intensity: 2000mJ / cm 2) or EB (EB irradiation device: Curetron EBC-200-AA3 manufactured by Nissin High Voltage Co., Ltd., accelerating voltage: 200 kV, exposure dose: 20 kGy). In the examples in which "UV then EB" is described as the curing method in Table 7, irradiation with UV rays was followed by further irradiation with EB rays. The obtained cured coating film was touched with a finger to check the state of adhesion of the coating composition to the finger, and curability was evaluated. In addition, the surface smoothness and transparency of the cured coating film were evaluated by visual observation. The evaluation results are shown in Table 7. In the appearance evaluation, when a pigment was contained, only the surface smoothness of the cured coating film was evaluated. Curability: ○: The coating composition no longer adheres. Δ: A small amount of the coating composition was adhered. ×: Paint composition adhered Coating appearance: ⊚: The surface was smooth and the coating film was transparent. ◯: The surface was smooth and the coating was generally transparent with slight cloudy areas. Δ: The surface was uneven or the coating had cloudy areas. ×: The surface was uneven and the coating film was cloudy.

[0103] <Wear resistance evaluation> The abrasion resistance of the obtained cured coating film was evaluated in accordance with ISO20566 using a car wash abrasion tester (Amtec laboratory Car Wash device manufactured by Amtec Kistler GmbH). The 20° gloss of the cured coating film before and after the abrasion test was measured using a gloss meter manufactured by BYK Gardner, the gloss retention was calculated using the following formula, and the abrasion resistance of the coating film was evaluated according to the following criteria. Note that the higher the gloss retention, the higher the abrasion resistance of the cured coating film. Gloss retention rate (%) = (gloss value after rubbing) / (gloss value before rubbing) x 100% Regarding the calculated gross retention rate, ○: Gross retention rate 80% or more △: Gross retention rate 60% or more but less than 80% ×: Gloss retention rate less than 60%

[0104] As is clear from the results in Table 7, the active energy ray curable coating compositions of the examples have good wettability to various substrates, excellent curability, and the appearance and abrasion resistance of the resulting cured coating film are good. On the other hand, the coating compositions of the comparative examples have low curability, and the appearance and abrasion resistance of the resulting cured coating film are low. The coating composition of the present invention has good wettability to a wide range of materials from general-purpose plastics to wood and metals, high curability to active energy rays, and good properties of the resulting cured coating film, and can be suitably used in a wide range of applications such as coatings for various electronic components, indoor and outdoor coatings, floor coatings, and vehicle coatings.

[0105] <Preparation and Evaluation of Active Energy Ray-Curable Sealant Composition> Examples 48 to 52 and Comparative Examples 17 and 18 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 8 and mixed uniformly at room temperature to prepare sealant compositions of Examples and Comparative Examples. Using the obtained sealant compositions, sealants (sealant cured products) were produced and their physical properties were evaluated by the following methods.

[0106] <Preparation of hardened sealant> A silicone spacer (30 mm long x 15 mm wide x 3 mm thick) was set on a glass plate (50 mm long x 50 mm wide x 5 mm thick), and copper foil (5 mm long x 50 mm wide x 80 μm thick) was placed inside the spacer, and the prepared active energy ray-curable sealant composition was injected. After sufficient degassing, the mixture was irradiated with ultraviolet light (apparatus: inverter type conveyor device ECS-4011GX manufactured by I-Graphics, metal halide lamp: M04-L41 manufactured by I-Graphics, ultraviolet light illuminance: 700 mW / cm 2 , Accumulated light intensity: 1000mJ / cm 2 The properties of the resulting cured product were evaluated by the following methods, and the results are shown in Table 8.

[0107] <Transparency evaluation of cured sealant> The obtained cured sealant product was left to stand for 24 hours in an atmosphere of 23°C and 50% relative humidity, and then the transmittance of the cured product was measured using a haze meter (NDH-2000, manufactured by Nippon Denshoku Industries Co., Ltd.) and the transparency was evaluated into the following four levels. ◎: Transmittance is 90% or more ○: Transmittance is 85% or more and less than 90% △: Transmittance is 50% or more and less than 85% ×: Transmittance is less than 50%

[0108] <Evaluation of resistance to moist heat yellowing> The obtained sealant cured product was left to stand for 24 hours in an atmosphere with a temperature of 23°C and a relative humidity of 50%, and then the transmission spectrum of the cured product was measured using a transmission color measuring instrument (TZ-6000, manufactured by Nippon Denshoku Industries Co., Ltd.) and was taken as the initial b value. The cured product was then left to stand for 500 hours in a thermohygrostat set at 85°C and a relative humidity of 85%, and an accelerated test of wet heat yellowing resistance was performed. The cured product after the test was also left to stand for 24 hours in an atmosphere with a temperature of 23°C and a relative humidity of 50%, and the transmission color was measured and taken as the post-humid heat b value. The difference between the post-humid heat b value and the initial b value was taken as the change value Δb (Δb = post-humid heat b value - initial b value). The wet heat yellowing resistance of the cured product was evaluated in four stages as follows. ⊚: Both the initial b value and the b value after moist heat are 0.2 or less, and Δb is 0.1 or less. ◯: Either one or both of the initial b value and the b value after moist heat treatment exceeds 0.2, but both are 0.5 or less, and Δb is 0.2 or less. Δ: Either one or both of the initial b value and the b value after moist heat treatment exceeds 0.5, but both are 1.0 or less, and Δb is 0.3 or less. ×: Either or both of the initial b value and the b value after moist heat treatment exceed 1.0, or Δb exceeds 0.3.

[0109] <Water resistance evaluation of cured sealant> A 1g piece was cut out from the obtained cured product and placed in a thermo-hygrostat at 85°C and 95% relative humidity as a test piece. After leaving it for 48 hours, the weight of the test piece was measured again, and the water absorption rate was calculated using the following formula, and the water resistance was evaluated into four levels as shown below. The lower the water absorption rate, the higher the water resistance of the cured product. The lower the water absorption rate, the higher the water resistance. Water absorption rate (%) = (weight after water absorption - weight before water absorption) / weight before water absorption × 100% ◎: Water absorption rate is less than 1.0% ○: Water absorption rate is 1.0% or more and less than 2.0% △: Water absorption rate is 2.0% or more and less than 3.0% ×: Water absorption rate is 3.0% or more

[0110] <Outgassing resistance evaluation> A 1g piece was cut out from the obtained cured product, and placed in a thermostatic chamber set at 100°C as a test piece, and a dry nitrogen gas flow was passed through it for 24 hours. The weight of the test piece was then measured again, and the outgassing rate was calculated using the following formula and rated into four levels. The lower the outgassing rate, the higher the outgassing resistance. Outgassing rate (%) = (weight after test - weight before test) / weight before test x 100% ◎: Incidence rate is less than 0.1% ○: The incidence rate is 0.1% or more and less than 0.3% △: Incidence rate is 0.3% or more and less than 1.0% ×: Incidence rate is 1.0% or more

[0111] <Heat cycle resistance evaluation> The resulting cured product was subjected to a cycle of leaving it at -40°C for 30 minutes and then at 100°C for 30 minutes, which was repeated 100 times. The condition of the cured product was visually observed and the heat cycle resistance was evaluated into 4 stages. ◎: No change was observed. ◯: A few bubbles are observed, but no cracks are observed. Transparent. Δ: A few bubbles or cracks were observed, and the film was slightly cloudy. ×: Bubbles or cracks are generated over the entire surface, and the surface is semi-transparent.

[0112] <Corrosion resistance evaluation> After the above-mentioned wet heat yellowing resistance test, the surface of the copper foil was visually observed and the corrosion resistance of the cured product was evaluated into four stages. ◎: No corrosion ○: Slight corrosion △: Slightly corroded ×: Severe corrosion Corrosion resistance was evaluated, and the results are shown in Table 5.

[0113] As is clear from the results in Table 8, the sealant cured products obtained from the active energy ray-curable sealant compositions of the Examples had high transparency and water resistance, generated little outgas, and had good resistance to wet heat yellowing and metal corrosion (corrosion resistance). On the other hand, these physical properties were not observed in the cured products obtained from the curable compositions of the Comparative Examples. The sealant composition of the present invention can be suitably used as a sealant for optical members, electrical devices, etc.

[0114] <Preparation and Evaluation of Active Energy Ray-Curable Nail Cosmetics> Examples 53 to 58 and Comparative Examples 19 and 20 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 9 and mixed uniformly at room temperature to prepare nail cosmetics of Examples and Comparative Examples. Using the obtained nail cosmetics, the curability and physical properties of the obtained cured film were evaluated by the following methods.

[0115] <Evaluation of the hardening properties of nail cosmetics> The active energy ray curable nail cosmetics prepared in the examples and comparative examples were applied to a nylon 6 test piece ("SHT-N6(NC)" manufactured by Toray Plastics Precision Co., Ltd.) using a bar coater to a film thickness of 10 μm, and then irradiated with ultraviolet light using a UV LED lamp for gel nails (manufactured by Beauty Nailer, wavelength 405 nm, 48 W). The time it took for the tackiness to disappear when touching the surface of the cured film was evaluated into four stages. The shorter the time required for the tackiness to disappear, the higher the curability. ◎: Tack disappears in less than 1 minute. ○: Tack disappears in 1 minute or more but less than 3 minutes. △: The tack disappears in 3 minutes or more but less than 10 minutes. ×: The tack does not disappear even after 10 minutes or more.

[0116] <Adhesion (nylon substrate) evaluation> The photocurable nail cosmetic of each of the examples and comparative examples obtained was applied to a nylon 6 test piece in the same manner as above, and a cured film was produced by irradiating light for 3 minutes. Using the obtained cured film, 100 1 mm square checkerboards were made with a cutter knife in accordance with JIS K 5600, and the number of checkerboards remaining on the test piece when a commercially available cellophane tape was attached and then peeled off was evaluated into 4 levels. The more checkerboards remaining on the test piece, the higher the adhesion. ◎: The number of remaining squares is 100. ○: The number of remaining grids is 90 to 99. △: The number of remaining squares is 60 to 89. ×: The number of remaining squares is less than 60.

[0117] <Evaluation of surface hardness of cured film> Similarly to the adhesion evaluation, cured films of each Example and Comparative Example were prepared, and the surface of the obtained film was drawn with a pencil of hardness HB under a load of 750 g, and the presence or absence of peeling and scratches was visually confirmed and rated into three stages. The fewer scratches and peeling, the higher the surface hardness. A: No scratches or peeling occurred. The surface hardness is pencil hardness HB or higher. △: No peeling occurred, but scratches occurred. ×: Peeling occurred.

[0118] <Surface gloss evaluation> In the same manner as in the adhesion evaluation, cured films were prepared for each of the Examples and Comparative Examples, and the gloss of the film surface was visually observed and rated into three levels. ○: Shiny. △: Light reflection can be confirmed, but there is some cloudiness. ×: No light reflection was observed and there was no gloss.

[0119] As is clear from the results in Table 9, the active energy ray curable nail cosmetic of the Example had excellent curability compared to a commercially available UV lamp for gel nails, while also having high adhesion to a nylon substrate (a material having many amide groups similar to nails, whose main component is protein). From these results, it can be seen that the active energy ray curable nail cosmetic of the present invention can be suitably used as a gel nail base gel that is applied directly to the nail. In addition, the surface hardness and surface gloss of the obtained cured film are good, and it can also be suitably used as a gel nail top coat. On the other hand, the curable composition of the Comparative Example had low curability, and the surface hardness and surface gloss of the cured film were low.

[0120] <Preparation and evaluation of active energy ray curable decorative coating agent> Examples 59 to 63 and Comparative Examples 21 and 22 The active energy ray curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the proportions shown in Table 10 and mixed uniformly at room temperature to prepare decorative coating agents (active energy ray curable compositions used for decorative molding and decorative processing of decorative films, decorative sheets, etc.) of Examples and Comparative Examples. Using the obtained decorative coating agents, laminates were produced by the following decorative processing, and the physical properties of the obtained laminates were evaluated.

[0121] <Preparation of Laminate> The resulting decorative coating agent was applied to a 180 μm thick PC film ("Panlite PC-2151" manufactured by Teijin Ltd.) using a bar coater (RDS 6) so that the film thickness after drying would be 5 μm. The film was then heated at 80°C for 3 minutes and irradiated with ultraviolet light (high pressure mercury lamp 300 mW / cm 2 , 1,000mJ / cm 2) to cure the coating, thereby obtaining a laminate having a hard coat layer. The obtained laminate was cut out, and the surface tack resistance, elongation, pencil hardness, scratch resistance, bending resistance, and sunscreen agent resistance of the hard coat layer were evaluated by the following methods, and the results are shown in Table 10. In Examples 57 and 60, the laminate after curing with active energy rays was placed in a thermostatic chamber at 80°C, and heated for 8 hours, after which various physical properties were evaluated.

[0122] <Evaluation of surface tack resistance> The surface of the film of the obtained laminate was touched with a finger to evaluate the stickiness. ◎: Not sticky at all. Good: Slightly sticky, but finger marks do not remain on the surface. △: Sticky and leaves finger marks on the surface. ×: Extremely sticky, fingers stick to the surface.

[0123] <Growth rate evaluation> The obtained laminate was cut to a length of 50 mm and a width of 15 mm, and fixed to a Tensilon universal testing machine RTA-100 (manufactured by Orientec Co., Ltd.) with a chuck distance of 25 mm, and pulled in one direction at a speed of 250 mm / min in an oven set at a temperature of 150° C. while visually observing the appearance, and the length (mm) of the test piece when cracks or whitening occurred in the coating layer was measured. The elongation was calculated and evaluated by the following method. Elongation (%) = (length of specimen after test / 25) x 100% ◎: Elongation rate is 200% or more ○: Elongation rate is 150% or more but less than 200% △: Elongation rate is 110% or more but less than 150% ×: Elongation rate is less than 110%

[0124] <Surface hardness evaluation> Using a test piece of the laminate, a pencil was used to scratch approximately 10 mm at a 45° angle in accordance with JIS K 5600, and the pencil hardness of the hardest pencil that did not scratch the surface of the laminate was recorded as the pencil hardness, and the surface hardness was evaluated as follows. ◎: Pencil hardness is 2H or more ○: Pencil hardness is HB~H △:Pencil hardness is 3B~B ×: Pencil hardness is 4B or less

[0125] <Scratch resistance evaluation> A test piece of the laminate was subjected to 10 passes of #0000 steel wool with a load of 200 g, and the surface of the laminate was visually observed to evaluate scratch resistance. ⊚: No peeling or damage to the film was observed. ○: Slight fine scratches are observed in some parts of the film. △: Streak-like scratches are observed throughout the membrane. ×: Peeling of the film occurs.

[0126] <Evaluation of bending resistance> A test piece of the laminate was folded 180° so that the coated surface was on the outside, a 1 kg weight was placed on it and left for 10 minutes, and the surface of the laminate was visually observed for cracks to evaluate folding resistance. .circle.: No cracks were observed. ◯: The folded portion was partially whitened. △: Some cracks were observed at the bent portion. ×: Cracks were observed at the bent portion.

[0127] <Evaluation of resistance to sunscreen agents> A sunscreen, UltraSheer DRY-TOUCH SUNSCREEN SPF100+ (Johnson & Johnson), was applied to the coated surface of the laminate test piece to a diameter of approximately 1 cm, heated at 80°C for 6 hours, allowed to cool, and then washed off with a neutral detergent. The surface condition was observed, and the sunscreen resistance was evaluated as follows. ◎: No traces of sunscreen were found. ○: Slightly transparent marks are visible on the areas where sunscreen was applied. △: White marks remain on the areas where sunscreen was applied, and the surface is swollen. ×: The area where the sunscreen was applied was sticky and the surface was peeling off.

[0128] As is clear from the results in Table 10, a laminate having a decorative coating layer (decorative coating film) could be easily obtained by applying the active energy ray curable decorative coating agent of the embodiment to the surface of a general-purpose plastic substrate and curing it with active energy rays. The surface (coated surface) of the obtained laminate has tack resistance, high hardness, and excellent scratch resistance and sunscreen resistance. In addition, the elongation rate and bending resistance of the obtained laminate were good. In particular, after curing with active energy rays, the stress between the coated surface and the substrate was further relaxed by heat treatment, and when the cyclic substituent of the (meth)acrylate (A), which is an essential component of the decorative coating agent, has an unsaturated bond, the unsaturated bond is thermally polymerized in the heat treatment process, and the surface (coated surface) hardness, scratch resistance, and sunscreen resistance were further improved. On the other hand, the curable composition of the comparative example did not have a similar decorative performance. The decorative coating agent of the present invention is suitable for a wide variety of decorative molding, decorative processing, and decorative printing such as decorative films, decorative sheets, and decorative coatings.

[0129] <Preparation and evaluation of active energy ray-curable dental materials> Examples 64 to 68 and Comparative Examples 23 and 24 The active energy ray curable composition, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C) and other components obtained in Table 2 were weighed and mixed uniformly at room temperature to prepare an active energy ray curable dental material. The solubility or dispersibility of the dental material (when an insoluble inorganic filler, pigment, etc. was blended) was visually observed, and the storage stability was evaluated, and the results are shown in Table 11. In addition, a dental material was used to prepare a dental material cured product by the following method, and the curability of the dental material, the surface smoothness, hardness, and adhesive strength of the obtained dental material cured product were evaluated, and the results are shown in Table 11. In addition, in Examples 62 and 65, the cured product after active energy ray curing was placed in a thermostatic chamber at 80°C and heated for 8 hours, and various physical properties were evaluated.

[0130] <Solubility (dispersibility) evaluation> ⊚: The composition obtained was homogeneous and transparent. ◯: The composition obtained was homogeneous and translucent. Δ: The composition obtained was cloudy and its uniformity was difficult to judge. ×: The composition obtained was not completely mixed.

[0131] <Storage stability evaluation> The obtained compositions of the Examples and Comparative Examples were placed in light-shielding screw tubes, the lids were closed, and the compositions were stored under two conditions: at 40° C. for one month and at 80° C. for two weeks. The state of dissolution or dispersion of the compositions after storage was confirmed to evaluate storage stability. ○: No change in condition was observed after storage at 40°C for one month and at 80°C for two weeks. △: A change in state was observed after storage under either one of the following conditions: 40°C for one month or 80°C for two weeks. ×: Changes in condition were observed after storage at 40°C for one month and at 80°C for two weeks.

[0132] <Curing evaluation> The obtained compositions of the Examples and Comparative Examples were filled into a polytetrafluoroethylene mold (20 mm × 20 mm × 10 mm) having a hole of 6 mm diameter in the center, and pressed with a polypropylene film. The mold was then placed in a dental light irradiator (Tokuso Power Light, manufactured by Tokuyama Dental Co., Ltd., light output density 700 mW / cm 2 , light intensity at the irradiation surface is 640-650mW / cm 2 A light source (halogen lamp, irradiation aperture 8 mm) was placed in close contact with the polypropylene film and irradiated for 30 seconds, after which the polypropylene film was peeled off and the cured product was touched with the hand to check for stickiness and the presence or absence of uncured components. ◎: No stickiness at all (completely cured). ○: There is some stickiness, but no finger marks remain on the surface (almost completely cured, no need to wipe off uncured components). △: Sticky and finger marks remain on the surface (incomplete curing, uncured components need to be wiped off). ×: Extremely sticky, fingers stick to the surface (a large amount of uncured components remain, and the film cannot be used as a cured film).

[0133] <Surface smoothness> The surface of the cured product obtained in the above curability evaluation was visually observed to confirm the smoothness and gloss, and the surface smoothness was evaluated. ◎: The surface is smooth and glossy. ◯: The surface is almost smooth, with slight cloudiness or slight irregularities. △: The surface is generally cloudy, and some irregularities and granularity are observed. ×: The surface is entirely cloudy and covered with granular matter.

[0134] <Hardness evaluation> The surfaces of the cured products obtained in the above curability evaluation were buffed and used to measure the Knoop hardness at a load of 10 g for 20 seconds using a Matsuzawa Seiki Microhardness Tester. The measurement temperature was 23°C. ◎: Knoop hardness is 200KHN or higher (equivalent to permanent tooth enamel). ○: Knoop hardness is 70KHN or more and less than 200KHN (equivalent to dentin). △: Knoop hardness is less than 70KHN. ×: Not cured, so measurement was not possible.

[0135] <Adhesion strength (dentin adhesion strength)> A bovine mandibular anterior tooth was polished with #1000 waterproof abrasive paper under water, a flat dentin surface for bonding was scraped off, compressed air was blown onto it for 10 seconds to dry it, and a tape with a hole of 3 mm in diameter was attached to set the adhesion surface. Then, an adhesion test piece was prepared by a known method (see the method described in JP 2010-208964 A). The adhesion test piece was immersed in 37°C water for 24 hours, and then the tensile adhesion strength was measured using an Instron universal testing machine (crosshead speed 2 mm / min), and the adhesion strength of the composition obtained in the examples and comparative examples to enamel and dentin was determined. The tensile adhesion strength value was the average value of five test pieces. ◎: The adhesive strength of both enamel and dentin is 20Mpa or more. ○: The adhesive strength between enamel and dentin is 20Mpa or more at least in one of the two locations. △: The adhesive strength of both enamel and dentin is 7Mpa or more. ×: The adhesive strength between enamel and dentin is less than 7 MPa.

[0136] As is clear from the results in Table 11, the active energy ray-curable dental materials of the Examples have high solubility (or dispersibility), curability, and storage stability, and the cured products obtained by curing them have good hardness, surface smoothness, and adhesive strength. On the other hand, the compositions of the Comparative Examples have low solubility, curability, and storage stability, and do not cure sufficiently, so that the hardness and surface smoothness of the obtained cured products are low, and the adhesive strength is insufficient.

[0137] As shown in the evaluation results of each of the above-mentioned Examples and Comparative Examples, the active energy ray curable composition containing the (meth)acrylate (A) having a specific structure and the polymerizable compound (B) according to the present invention has high transparency and good curability due to the cyclic substituent of A and the amide, while having good wettability and adhesion to various substrates, and the cured product obtained by curing them has excellent water resistance, heat resistance, impact resistance, abrasion resistance, etc. It can be seen. The curable composition has low cure shrinkage caused by the interaction between the (meth)acrylate (A) and the polymerizable compound (B) when the composition is cured, and the cured product obtained does not have internal stress or distortion, so the durability was good. On the other hand, it is clear that the curable composition and the cured product thereof not containing the (meth)acrylate (A) or the polymerizable compound (B) do not have the various physical properties described above. That is, it was confirmed that the various physical properties of the active energy ray curable composition of the present invention and the cured product obtained therefrom are due to the interaction between the (meth)acrylate (A) and the polymerizable compound (B) contained therein.

[0138] [Table 1]

[0139] [Table 2]

[0140] [Table 3]

[0141] [Table 4]

[0142] [Table 5]

[0143] [Table 6]

[0144] [Table 7]

[0145] [Table 8]

[0146] [Table 9]

[0147] [Table 10]

[0148] [Table 11] [Industrial Applicability]

[0149] As described above, the active energy ray curable composition of the present invention contains a specific (meth)acrylate (A) and a polymerizable compound (b1) having a chain-like substituent and / or a polymerizable compound (b2) having a cyclic substituent, and thus has high transparency and good curability, and is excellent in wettability to various substrates having a wide range of polarities from low polarity to high polarity, and can obtain a cured product having low curing shrinkage, excellent water resistance, impact resistance, abrasion resistance, and durability. The curable composition can be used in active energy ray curable ink compositions, ink compositions for two-dimensional or three-dimensional modeling, pressure-sensitive adhesive compositions, adhesive compositions, paint compositions, sealant compositions, nail cosmetics, decorative coating agents, dental materials, etc.

Claims

1. a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule; An active energy ray-curable composition containing a polymerizable compound (B) (excluding A) having one or more (meth)acrylamide groups and / or (meth)acrylate groups in the molecule, the polymerizable compound (B) comprises a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms; The content of (A) is 0.5 to 99.5 mass% based on the total amount of the active energy ray-curable composition, When (b1) is contained, the content thereof is 0.3 to 80 mass %; When (b2) is contained, the content thereof is 0.2 to 70 mass %; An active energy ray-curable composition having a cure shrinkage rate of 5% or less.

2. 2. The active energy ray-curable composition according to claim 1, wherein the (meth)acrylate (A) has, as a cyclic substituent, one or more substituents selected from a saturated or unsaturated polycyclic aliphatic ring, a monocyclic or polycyclic aromatic ring, a saturated or unsaturated aliphatic heterocycle, and an aromatic heterocycle.

3. 3. The active energy ray-curable composition according to claim 1, wherein the (meth)acrylate (A) has an amide group between the (meth)acrylate group and the cyclic substituent.

4. A composition described in any one of claims 1 to 3, wherein the (meth)acrylate (A) has a cyclic substituent that is an unsaturated ring or the cyclic substituent further has an unsaturated substituent.

5. 5. The active energy ray-curable composition according to claim 1, wherein a cured product of the active energy ray-curable composition has a saturated water absorption of 10% or less.

6. An ink composition comprising the active energy ray-curable composition according to any one of claims 1 to 5.

7. An ink composition for two-dimensional or three-dimensional modeling, comprising the active energy ray-curable composition according to any one of claims 1 to 5.

8. A pressure-sensitive adhesive composition comprising the active energy ray-curable composition according to any one of claims 1 to 5.

9. An adhesive composition comprising the active energy ray-curable composition according to any one of claims 1 to 5.

10. A coating composition comprising the active energy ray-curable composition according to any one of claims 1 to 5.

11. A sealant composition comprising the active energy ray-curable composition according to any one of claims 1 to 5.

12. A nail cosmetic comprising the active energy ray-curable composition according to any one of claims 1 to 5.

13. A decorative coating agent comprising the active energy ray-curable composition according to any one of claims 1 to 5.

14. A dental material comprising the active energy ray-curable composition according to any one of claims 1 to 5.